Bonding conductor paste

By adding urea compounds and hydroxyl-containing ether solvents to the conductor paste, the problems of solvent leakage and pore generation in the prior art are solved, and printing suitability and bonding strength are improved.

CN119866528APending Publication Date: 2025-04-22DAICEL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380065867.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-14
Filing Date
2023-09-08
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, conductor pastes using ether solvents are prone to solvent leakage, resulting in printing defects, and pores in large-area chips, reducing bondability.

Method used

The bonding conductor paste containing conductive particles, a hydroxyl-containing ether solvent and a urea compound is used to inhibit solvent leakage and pore generation by adjusting the content of the urea compound and using a dispersion medium containing the hydroxyl-containing ether solvent.

Benefits of technology

It improves printing suitability, reduces the generation of pores, and enhances the bonding strength of conductor wiring and bonding structure, which is suitable for applications in connecting electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866528A_ABST
    Figure CN119866528A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a bondable conductor paste which is capable of improving printing suitability by reducing solvent bleeding and improving bondability by reducing the occurrence of voids. This adhesive conductor paste contains conductive particles, a dispersion medium containing a hydroxyl group-containing ether solvent, and a urea compound. The content ratio of the urea compound is 1-20 parts by mass per 100 parts by mass of the entire dispersion medium containing the hydroxyl group-containing ether solvent, or the content ratio of the urea compound is 0.1-2 parts by mass per 100 parts by mass of the conductive particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a bonding conductor paste suitable for forming a sintered body such as a conductor wiring and a bonding structure for connecting electronic components. More specifically, the present disclosure relates to a bonding conductor paste suitable for forming a conductor wiring and a bonding structure for connecting electronic components such as power semiconductor components and LED components. This application claims priority to Japanese Patent Application No. 2022-146294 filed in Japan on September 14, 2022, the contents of which are incorporated herein by reference. Background Art

[0002] When mounting electronic components such as power semiconductor elements and LED elements, it is necessary to join a plurality of materials with high strength, and therefore, a conductor wiring, a joining structure, or a wiring substrate including these is used.

[0003] As a method for forming the above-mentioned conductor wiring, for example, a method is known in which a conductor paste containing conductive particles and an organic solvent is applied on an insulating substrate by a printing method and then sintered to produce the conductor wiring.

[0004] For example, Patent Document 1 discloses a bonding conductor paste containing conductive particles and a specific ether solvent, and states that: by using the bonding conductor paste, uniform printing can be performed to form a high-precision conductor wiring and a bonding structure that can connect a substrate and an electronic component with high bonding strength.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-194786 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, although the conductor paste using ether solvents has good wettability to the substrate, it is easy to cause solvent bleeding, sometimes causing printing defects. In addition, in large-area chips of 10 mm square or more, the solvent volatilization becomes insufficient, sometimes generating voids and causing reduced bonding.

[0010] Therefore, an object of the present disclosure is to provide an adhesive conductor paste capable of reducing solvent bleeding to improve printing suitability and reducing the generation of voids to improve adhesiveness.

[0011] Solutions to the problem

[0012] The inventors of the present disclosure have conducted intensive research to solve the above-mentioned problems, and as a result, have found that a bonding conductor paste containing conductive particles, a hydroxyl-containing ether solvent, and a urea compound can suppress solvent bleeding to improve printing suitability, and suppress the generation of voids during sintering to improve bonding. The present disclosure relates to a method completed based on these findings.

[0013] That is, the present disclosure provides a bonding conductor paste containing conductive particles, a dispersion medium containing a hydroxyl-containing ether solvent, and a urea compound.

[0014] The content ratio of the urea compound is 1 to 20 parts by mass based on 100 parts by mass of the entire dispersion medium containing the hydroxyl-containing ether solvent.

[0015] The present disclosure also relates to a bonding conductor paste comprising conductive particles, a dispersion medium containing a hydroxyl group-containing ether solvent, and a urea compound.

[0016] The content ratio of the urea compound is 0.1 to 2 parts by mass based on 100 parts by mass of the conductive particles.

[0017] In the bonding conductor paste, the hydroxyl-containing ether solvent may include a compound represented by the following formula (A):

[0018] R a -O-(R b -O) n -OH(A)

[0019] (In formula (A), R a represents an alkyl group, an aryl group or an aralkyl group, R b represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer greater than 1. )

[0020] In the bonding conductor paste, the urea compound may be at least one selected from the group consisting of modified urea, urea-modified urethane, polymer urea derivatives, and urea-modified polyamide.

[0021] In the bonding conductor paste, the conductive particles may include silver particles.

[0022] In the bonding conductor paste, the conductive particles may include conductive nanoparticles (A) having an average particle diameter of 1 nm or more and less than 100 nm.

[0023] The conductive nanoparticles (A) may be conductive nanoparticles having a structure in which the surface is coated with a protective agent containing amine.

[0024] In the bonding conductor paste, the proportion of the conductive nanoparticles (A) in the total amount (100% by mass) of the conductive particles contained in the bonding conductor paste may be 50% by mass or less.

[0025] In the bonding conductor paste, the protective agent in the conductive nanoparticles (A) is an amine.

[0026] It may contain an aliphatic hydrocarbon monoamine (1) comprising an aliphatic hydrocarbon group and one amino group, wherein the total number of carbon atoms of the aliphatic hydrocarbon group is 6 or more,

[0027] The invention further contains at least one of an aliphatic hydrocarbon monoamine (2) comprising an aliphatic hydrocarbon group and one amino group, wherein the total number of carbon atoms of the aliphatic hydrocarbon group is 5 or less, and an aliphatic hydrocarbon diamine (3) comprising an aliphatic hydrocarbon group and two amino groups, wherein the total number of carbon atoms of the aliphatic hydrocarbon group is 8 or less.

[0028] In the bonding conductor paste, the conductive particles may include, in addition to the conductive nanoparticles (A), spherical conductive particles (B) having an average particle size of 0.5 μm to 1 μm, and flat conductive flakes (C) having an average particle size of 1 μm to 10 μm.

[0029] In the bonding conductor paste, the total content of the conductive nanoparticles (A), the spherical conductive particles (B) and the flat conductive flakes (C) in the total amount (100% by mass) of the bonding conductor paste may be 80 to 99.5% by weight.

[0030] In the bonding conductor paste, the dispersion medium may include an organic solvent (a), an organic solvent (b), and an organic solvent (c), wherein the organic solvent (a), the organic solvent (b), and the organic solvent (c) are different compounds and satisfy the following formulas (1) to (6).

[0031] 150℃≤Ta≤250℃ (1)

[0032] 150℃≤Tb≤250℃ (2)

[0033] 250℃≤Tc≤350℃ (3)

[0034] δa≥10.0 (4)

[0035] δc≤9.0 (5)

[0036] δc≤δb≤δa (6)

[0037] [Wherein, Ta to Tc represent the boiling points of organic solvents (a) to (c), respectively, and δa to δc represent the Hansen solubility parameters of organic solvents (a) to (c), respectively.]

[0038] Furthermore, the present disclosure relates to a sintered body obtained by sintering a bonding conductor paste.

[0039] Furthermore, the present disclosure relates to a joined structure formed by joining using a sintered body formed by sintering a joining conductor paste.

[0040] Effects of the Invention

[0041] According to the bonding conductor paste disclosed in the present invention, it is possible to suppress the solvent from seeping out and suppress the generation of voids when forming a sintered body. Therefore, the printing suitability when forming a sintered body such as a conductor wiring, a bonding structure, etc. for connecting electronic components using the bonding conductor paste is improved, and since voids are not easily generated, it is possible to produce a sintered body such as a conductor wiring, a bonding structure, etc. having high bonding strength, and an electronic device having the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 (a) is a SAT image of the surface of the sintered body after the die shear strength of the sample prepared in Example 3 was measured. Figure 1 (b) is a SAT image of the sintered body surface of the sample prepared in Comparative Example 2 after the die shear strength was measured.

[0043] Figure 2 (a) is a SEM image of a cross section of a sintered body of a sample prepared in Example 3 after the die shear strength measurement. Figure 2 (b) is a SEM image of a cross section of a sintered body of the sample prepared in Comparative Example 2 after the die shear strength measurement. DETAILED DESCRIPTION

[0044] [Conductor paste for bonding]

[0045] The bonding conductor paste of the present disclosure is a paste composition that can form a conductor and use the conductor to bond members together. The bonding conductor paste is, for example, a bonding conductor paste for forming a sintered body (eg, conductor wiring, bonding structure) for connecting electronic components.

[0046] The bonding conductor paste contains conductive particles, a dispersion medium containing a hydroxyl group-containing ether solvent, and a urea compound. In the bonding conductor paste, the conductive particles are dispersed in the dispersion medium.

[0047] (Conductive particles)

[0048] The conductive particles are particles that are fused by sintering the bonding conductor paste to form a conductive sintered body. The conductive material constituting the conductive particles is not particularly limited as long as it has conductivity, and for example, metals, metal oxides, non-conductors coated with metal on the surface, semiconductor particles, etc. can be used.

[0049] As the metal constituting the above-mentioned conductive particles, metals with conductivity can be cited, for example, gold, silver, copper, nickel, aluminum, rhodium, cobalt, ruthenium, platinum, palladium, chromium, indium and their alloys. As the metal oxide constituting the above-mentioned conductive particles, metal oxides with conductivity can be cited, for example, chromium oxide, nickel oxide, copper oxide, titanium oxide, zirconium oxide, indium oxide, aluminum oxide, zinc oxide, tin oxide, or their composite oxides such as composite oxides of indium oxide and tin oxide (ITO), composite oxides of tin oxide and phosphorus oxide (PTO), etc. These conductive substances can be used alone or in combination of two or more. As the above-mentioned conductive substance, a metal with excellent conductivity is more preferred, and gold, silver, copper, etc. are more preferred. Among them, from the viewpoint of being mutually welded at a temperature of about 100°C and being able to form a connecting member such as a conductive electronic component even on a general plastic substrate with low heat resistance, silver is preferred. That is, as the above-mentioned conductive particles, silver particles are preferred.

[0050] The conductive particles preferably include conductive nanoparticles having an average particle diameter of 1 nm or more and less than 100 nm (sometimes referred to as "conductive nanoparticles (A)" in this specification), wherein the conductive nanoparticles have a structure in which the surface is coated with a protective agent containing an amine, and more specifically, have a structure in which the non-shared electron pairs of the amine are electrically coordinated to the surface of the conductive nanoparticles. The conductive nanoparticles (A) can prevent the re-agglomeration of the conductive nanoparticles by having the above-mentioned structure, and can stably maintain a highly dispersed state in the bonding conductor paste. Only one type of conductive nanoparticles (A) can be used, or two or more types can be used.

[0051] The average particle size of the conductive nanoparticles (A) is greater than 1 nm and less than 100 nm, preferably 2 to 80 nm, more preferably 5 to 70 nm, and further preferably 10 to 60 nm. The above average particle size is the size excluding the protective agent coating the surface (i.e., the size of the conductive nanoparticles themselves). It should be noted that the above average particle size is based on the particle size obtained by observation through a transmission electron microscope (TEM), assuming that the particles have an aspect ratio of 1, and is obtained in the form of an average particle size (median particle size) converted into a volume distribution. When the conductive nanoparticles (A) contain two or more types, the above average particle size refers to the average particle size of all conductive nanoparticles (A).

[0052] The conductive nanoparticles (A) are surface-modified conductive nanoparticles having a structure in which the surface of the conductive nanoparticles is coated with a protective agent containing an amine. The above-mentioned amine may be used alone or in combination of two or more. In addition, the above-mentioned protective agent may also contain a compound other than the above-mentioned amine.

[0053] The amine is a compound in which at least one hydrogen atom of ammonia is substituted with a hydrocarbon group, and examples thereof include primary amines, secondary amines, and tertiary amines. The amine may be a monoamine or a polyamine such as a diamine.

[0054] The amine preferably contains at least one selected from the group consisting of a monoamine (1) having a total carbon number of 6 or more, a monoamine (2) having a total carbon number of 5 or less, and a diamine (3) having a total carbon number of 8 or less, wherein the monoamine (1) is represented by the following formula (a-1), wherein R 1 , R 2 , R 3 The same or different are hydrogen atoms or monovalent hydrocarbon groups (excluding R 1 , R 2 , R 3 are all hydrogen atoms), the monoamine (2) is represented by the following formula (a-1), where R 1 , R 2 , R 3 The same or different are hydrogen atoms or monovalent hydrocarbon groups (excluding R 1 , R 2 , R 3 are all hydrogen atoms), the diamine (3) is represented by the following formula (a-2), where R 8 is a divalent hydrocarbon group, R 4 ~R 7 The same or different ones are hydrogen atoms or monovalent hydrocarbon groups, and it is particularly preferred to contain a monoamine (1) and a monoamine (2) and / or a diamine (3) in combination.

[0055] [Chemical formula 1]

[0056]

[0057] Examples of the hydrocarbon group include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, and an aromatic hydrocarbon group. Among them, an aliphatic hydrocarbon group and an alicyclic hydrocarbon group are preferred, and an aliphatic hydrocarbon group is particularly preferred. Therefore, as the monoamine (1), monoamine (2), and diamine (3), an aliphatic monoamine (1), an aliphatic monoamine (2), and an aliphatic diamine (3) are preferred.

[0058] Examples of the monovalent aliphatic hydrocarbon group include alkyl and alkenyl groups. Examples of the monovalent alicyclic hydrocarbon group include cycloalkyl and cycloalkenyl groups. Examples of the divalent aliphatic hydrocarbon group include alkylene and alkenylene groups. Examples of the divalent alicyclic hydrocarbon group include cycloalkylene and cycloalkenylene groups.

[0059] As R 1 , R 2 , R 3 The monovalent hydrocarbon group in the invention includes, for example, alkyl groups having about 1 to 20 carbon atoms, such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, decyl, dodecyl, tetradecyl and octadecyl; alkenyl groups having about 2 to 20 carbon atoms, such as vinyl, allyl, methallyl, 1-propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl and 5-hexenyl; cycloalkyl groups having about 3 to 20 carbon atoms, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cyclooctyl; cycloalkenyl groups having about 3 to 20 carbon atoms, such as cyclopentenyl and cyclohexenyl.

[0060] As R 4 ~R 7 The monovalent hydrocarbon group in, for example, in R 1 , R 2 , R 3 Examples of the monovalent hydrocarbon group in include hydrocarbon groups having 7 or less carbon atoms.

[0061] As R 8 The divalent hydrocarbon group in the formula (I) includes, for example, alkylene groups having 1 to 8 carbon atoms such as methylene, methylmethylene, dimethylmethylene, ethylene, propylene, trimethylene, tetramethylene, pentamethylene and heptamethylene; and alkenylene groups having 2 to 8 carbon atoms such as vinylene, propenylene, 1-butenylene, 2-butenylene, butadienylene, pentenylene, hexenylene, heptenylene and octenylene.

[0062] The above R 1 ~R 8 The hydrocarbon group in the formula (a) may have various substituents [e.g., halogen atoms, oxo groups, hydroxyl groups, substituted oxy groups (e.g., C 1-4 Alkoxy, C 6-10 Aryloxy, C 7-16 Aralkyloxy, C 1-4 acyloxy, etc.), carboxyl, substituted oxycarbonyl (e.g., C 1-4 Alkoxycarbonyl, C 6-10 Aryloxycarbonyl, C 7-16 The hydroxyl group and the carboxyl group may be protected by a protecting group commonly used in the field of organic synthesis.

[0063] The monoamine (1) is a compound having a function of imparting high dispersibility to the conductive nanoparticles (A), and examples thereof include: primary amines having a straight-chain alkyl group such as hexylamine, heptylamine, octylamine, nonylamine, decylamine, undecylamine, dodecylamine, tridecylamine, tetradecylamine, pentadecylamine, hexadecylamine, heptadecanylamine, octadecylamine, etc.; primary amines having a branched alkyl group such as isohexylamine, 2-ethylhexylamine, tert-octylamine; primary amines having a cycloalkyl group such as cyclohexylamine; primary amines having an alkenyl group such as oleylamine, etc.; N,N-dipropylamine, N,N-dibutylamine, N,N-di Secondary amines having a straight-chain alkyl group such as amylamine, N,N-dihexylamine, N,N-diheptylamine, N,N-dioctylamine, N,N-dinonylamine, N,N-didecylamine, N,N-diundecylamine, N,N-didodecylamine, and N-propyl-N-butylamine; secondary amines having a branched-chain alkyl group such as N,N-diisohexylamine and N,N-di(2-ethylhexyl)amine; tertiary amines having a straight-chain alkyl group such as tributylamine and trihexylamine; tertiary amines having a branched-chain alkyl group such as triisohexylamine and tri(2-ethylhexyl)amine, etc.

[0064] Among the monoamines (1), amines having a linear alkyl group having a total carbon number of 6 or more (particularly a primary amine) are preferred from the viewpoint of being able to further ensure the spacing between the amino group and other conductive nanoparticles when the amino group is adsorbed on the surface of the conductive nanoparticles, thereby improving the effect of preventing the conductive nanoparticles from agglomerating with each other. In addition, from the viewpoint of easy availability and easy removal during sintering, the upper limit of the total carbon number of the monoamine (1) is preferably about 18, more preferably 16, and particularly preferably 12. As the monoamine (1), hexylamine, heptylamine, octylamine, nonylamine, decylamine, undecylamine, dodecylamine, etc. are particularly preferred.

[0065] In addition, when an amine having a branched alkyl group (particularly a primary amine) is used among the monoamines (1), compared with the case of using an amine having a straight-chain alkyl group having the same total number of carbon atoms, high dispersibility can be imparted to the conductive nanoparticles (A) with a smaller amount due to the steric factor of the branched alkyl group. Therefore, the amine can be efficiently removed during sintering, especially at low temperature, and it is preferred from the viewpoint of obtaining a sintered body with better conductivity.

[0066] As the above-mentioned amine having a branched alkyl group, amines having a total carbon number of 6 to 16 (preferably 6 to 10) such as isohexylamine and 2-ethylhexylamine are particularly preferred. In particular, amines having a branched alkyl group having a structure in which a branch is generated at the second carbon atom from the nitrogen atom such as 2-ethylhexylamine are effective from the viewpoint of steric factors.

[0067] Among the monoamines (1), preferably used are aliphatic hydrocarbon monoamines containing an aliphatic hydrocarbon group and one amino group, wherein the total number of carbon atoms of the aliphatic hydrocarbon group is 6 or more.

[0068] Since the hydrocarbon chain of monoamine (2) is shorter than that of monoamine (1), it is considered that the function of imparting high dispersibility to the conductive nanoparticles is low. However, since the polarity is higher than that of monoamine (1), the coordination ability to the conductive nanoparticles is high, and it is considered that it has a complex formation promoting effect. In addition, since the hydrocarbon chain is short, it can be removed from the surface of the conductive nanoparticles in a short time (for example, 30 minutes or less, preferably 20 minutes or less) even in low-temperature sintering, and a sintered body with excellent conductivity can be obtained.

[0069] Examples of the monoamine (2) include primary amines having a linear or branched alkyl group with a total number of carbon atoms of 2 to 5, such as ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, sec-butylamine, tert-butylamine, pentylamine, isopentylamine, and tert-pentylamine; and secondary amines having a linear or branched alkyl group with a total number of carbon atoms of 2 to 5, such as N-methyl-N-propylamine, N-ethyl-N-propylamine, N,N-dimethylamine, and N,N-diethylamine.

[0070] As the monoamine (2), among them, preferred are primary amines having a linear or branched alkyl group with a total carbon number of 2 to 5 (preferably a total carbon number of 4 to 5), such as n-butylamine, isobutylamine, sec-butylamine, tert-butylamine, pentylamine, isopentylamine, tert-pentylamine, and particularly preferred are primary amines having a linear alkyl group with a total carbon number of 2 to 5 (preferably a total carbon number of 4 to 5), such as n-butylamine.

[0071] Among them, the monoamine (2) is preferably an aliphatic hydrocarbon monoamine (2) containing an aliphatic hydrocarbon group and one amino group, wherein the total number of carbon atoms in the aliphatic hydrocarbon group is 5 or less.

[0072] The total number of carbon atoms of the diamine (3) is 8 or less (e.g., 1 to 8). Since the polarity is higher than that of the monoamine (1), the coordination ability for the conductive nanoparticles is high, and therefore it is considered to have a complex formation promoting effect. In addition, the diamine (3) has the effect of promoting thermal decomposition at a lower temperature and in a shorter time in the thermal decomposition process of the complex. When the diamine (3) is used, the conductive nanoparticles (A) can be produced more efficiently. In addition, the conductive nanoparticles (A) having a structure coated with a protective agent containing the diamine (3) exhibit excellent dispersion stability in a dispersion medium containing a highly polar solvent. In addition, since the diamine (3) has a short hydrocarbon chain, it can be removed from the surface of the conductive nanoparticles in a short time (e.g., 30 minutes or less, preferably 20 minutes or less) even in low-temperature sintering, and a sintered body with excellent conductivity can be obtained.

[0073] Examples of the diamine (3) include ethylenediamine, 1,3-propylenediamine, 2,2-dimethyl-1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, and 1,5-diamino-2-methylpentane. 4 ~R 7 is a hydrogen atom and R 8 is a linear or branched alkylene diamine; N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyl-1,3-propylenediamine, N,N'-diethyl-1,3-propylenediamine, N,N'-dimethyl-1,4-butanediamine, N,N'-diethyl-1,4-butanediamine, N,N'-dimethyl-1,6-hexanediamine. 4 , R 6 are identical or different linear or branched alkyl groups, R 5 , R 7 is a hydrogen atom and R 8 is a linear or branched alkylene diamine; N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dimethyl-1,3-propylenediamine, N,N-diethyl-1,3-propylenediamine, N,N-dimethyl-1,4-butylenediamine, N,N-diethyl-1,4-butylenediamine, N,N-dimethyl-1,6-hexanediamine. 4 , R 5 are identical or different linear or branched alkyl groups, R 6 , R 7 is a hydrogen atom and R 8 It is a linear or branched alkylene diamine, etc.

[0074] Among them, R in formula (a-2) is preferably 4 , R 5 are identical or different linear or branched alkyl groups, R 6 , R 7 is a hydrogen atom and R 8 is a linear or branched alkylene diamine [especially R in formula (a-2) 4 , R 5 is a straight-chain alkyl group, R 6 , R 7 is a hydrogen atom and R 8 is a straight-chain alkylene diamine].

[0075] For R in formula (a-2) 4 , R 5 are identical or different linear or branched alkyl groups and R 6 , R 7In the case of a diamine having a hydrogen atom, i.e., a diamine having a primary amino group and a tertiary amino group, although the primary amino group has a high coordination ability to a metal atom, the tertiary amino group lacks coordination ability to a metal atom, and thus, the formed complex can be prevented from being excessively complicated, thereby enabling thermal decomposition at a lower temperature and in a shorter time in the thermal decomposition step of the complex. Among them, from the viewpoint of being able to be removed from the surface of the conductive nanoparticles in a short time during low-temperature sintering, a diamine having a total carbon number of 6 or less (e.g., 1 to 6) is preferred, and a diamine having a total carbon number of 5 or less (e.g., 1 to 5) is more preferred.

[0076] Among them, the diamine (3) is preferably an aliphatic hydrocarbon diamine (3) containing an aliphatic hydrocarbon group and two amino groups, wherein the total number of carbon atoms in the aliphatic hydrocarbon group is 8 or less.

[0077] When the above-mentioned amines contain a monoamine (1) and a monoamine (2) and / or a diamine (3) in combination, the ratio of these amines to be used is not particularly limited, but is preferably in the following range based on the total amount of amines [monoamine (1) + monoamine (2) + diamine (3); 100 mol %].

[0078] Content of monoamine (1): for example, 5 to 65 mol% (the lower limit is preferably 10 mol%, more preferably 15 mol%. The upper limit is preferably 50 mol%, more preferably 40 mol%, and further preferably 35 mol%)

[0079] Total content of monoamine (2) and diamine (3): for example, 35 to 95 mol% (the lower limit is preferably 50 mol%, more preferably 60 mol%, and even more preferably 65 mol%. The upper limit is preferably 90 mol%, and more preferably 85 mol%)

[0080] When monoamine (2) and diamine (3) are used together, the content of each of monoamine (2) and diamine (3) is preferably within the following ranges based on the total amount of amines [monoamine (1) + monoamine (2) + diamine (3); 100 mol %].

[0081] Monoamine (2): for example, 5 to 70 mol% (the lower limit is preferably 10 mol%, more preferably 15 mol%. The upper limit is preferably 65 mol%, more preferably 60 mol%)

[0082] Diamine (3): for example, 5 to 50 mol% (the lower limit is preferably 10 mol%. The upper limit is preferably 45 mol%, more preferably 40 mol%)

[0083] When the content of the monoamine (1) is at least the above lower limit, the dispersion stability of the conductive nanoparticles is excellent, whereas when it is at most the above upper limit, the amine tends to be easily removed by low-temperature sintering.

[0084] When the content of the monoamine (2) is within the above range, the complex formation promoting effect is easily obtained. In addition, sintering can be performed at a low temperature and in a short time, and the diamine (3) is easily removed from the surface of the conductive nanoparticles during sintering.

[0085] When the content of the diamine (3) is within the above range, the complex formation promoting effect and the complex thermal decomposition promoting effect are easily obtained. In addition, the surface-modified conductive nanoparticles (A) having a structure coated with a protective agent containing diamine (3) exhibit excellent dispersion stability in a dispersion medium containing a highly polar solvent.

[0086] In the above-mentioned bonding conductor paste, when monoamine (2) and / or diamine (3) with high coordination ability for conductive nanoparticles are used, the amount of monoamine (1) can be reduced according to their usage ratio. Under the condition of low-temperature and short-time sintering, these amines are easily removed from the surface of conductive nanoparticles, which enables the sintering of conductive nanoparticles to proceed fully.

[0087] The amine used as the organic protective agent may contain other amines in addition to the monoamine (1), the monoamine (2) and the diamine (3). The total content of the monoamine (1), the monoamine (2) and the diamine (3) in the total amines contained in the protective agent is preferably 60% by mass or more (e.g., 60 to 100% by mass), more preferably 80% by mass or more, and even more preferably 90% by mass or more. That is, the content of the other amines is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less.

[0088] The amount of the amines [especially monoamine (1) + monoamine (2) + diamine (3)] used is not particularly limited, but is preferably about 1 to 50 mol per 1 mol of the conductive substance as a raw material of the conductive nanoparticles. From the viewpoint of obtaining surface-modified conductive nanoparticles (A) in the substantial absence of a solvent, it is preferably 2 to 50 mol, and particularly preferably 6 to 50 mol. When the amount of the amines used is equal to or greater than the lower limit, the conductive substance that has not been converted into a complex is unlikely to remain in the complex formation step, and in the subsequent thermal decomposition step, the uniformity of the conductive nanoparticles becomes high, and enlargement of the particles and the residue of the conductive substance that has not been thermally decomposed can be suppressed.

[0089] The protective agent may include other protective agents other than the amine. Examples of the other protective agent include aliphatic monocarboxylic acids. The use of aliphatic monocarboxylic acids tends to further improve the dispersibility of the conductive nanoparticles (A).

[0090] Examples of the aliphatic monocarboxylic acid include saturated aliphatic monocarboxylic acids having 4 or more carbon atoms, such as butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, nonadecanoic acid, and eicosanoic acid; and unsaturated aliphatic monocarboxylic acids having 8 or more carbon atoms, such as oleic acid, elaidic acid, linoleic acid, palmitoleic acid, and eicosenoic acid.

[0091] Among them, saturated or unsaturated aliphatic monocarboxylic acids having 8 to 18 carbon atoms (especially octanoic acid, oleic acid, etc.) are preferred. When the carboxyl group of the above-mentioned aliphatic monocarboxylic acid is adsorbed on the surface of the conductive nanoparticles, the saturated or unsaturated aliphatic hydrocarbon chain having 8 to 18 carbon atoms forms a steric hindrance, thereby ensuring the spacing with other conductive nanoparticles, and improving the effect of preventing the conductive nanoparticles from agglomerating with each other. In addition, from the viewpoint of easy acquisition and easy removal during sintering, the above-mentioned aliphatic monocarboxylic acid is also preferred.

[0092] The amount of the aliphatic monocarboxylic acid used is, for example, about 0.05 to 10 moles, preferably 0.1 to 5 moles, and more preferably 0.5 to 2 moles, relative to 1 mole of the conductive material constituting the conductive nanoparticles. When the amount of the aliphatic monocarboxylic acid used is greater than the lower limit, the stability improvement effect is more easily obtained. When the amount is less than the upper limit, the effect of the aliphatic monocarboxylic acid can be fully obtained, and excess aliphatic monocarboxylic acid is less likely to remain.

[0093] The conductive nanoparticles (A) coated with a protective agent containing an amine can be prepared by a known or customary method. For example, the conductive nanoparticles (A) can be prepared by the following steps: a step of mixing a compound containing a conductive substance and a protective agent containing an amine to generate a complex containing the compound and the amine (complex generation step); a step of thermally decomposing the complex (thermal decomposition step); and a step of washing the reaction product as needed (washing step).

[0094] The bonding conductor paste may contain other conductive particles in addition to the conductive nanoparticles (A). In particular, from the viewpoint of being able to form a conductor wiring and a bonding structure with lower resistance and excellent electrical properties, it is preferred to use a combination of conductive particles (groups) having different average particle sizes in the bonding conductor paste.

[0095] Examples of the shape of the other conductive particles include spherical, flat, and polyhedral shapes. Conductive particles having different shapes may be used in combination, or only conductive particles having the same shape may be used.

[0096] As the other conductive nanoparticles, particularly preferred are spherical conductive particles (B) having an average particle diameter of 0.5 to 1 μm and flat conductive flakes (C) having an average particle diameter of 1 to 10 μm.

[0097] (Spherical conductive particles (B))

[0098] When the conductive nanoparticles (A) and the spherical conductive particles (B) having a size larger than the conductive nanoparticles (A) are combined, the conductive nanoparticles (A) having a relatively small diameter are filled in the gaps between the spherical conductive particles (B) having a relatively large diameter in the formed sintered body, and a more dense conductor wiring and a joint structure can be formed, and a material having high bonding strength and high conductivity can be obtained. The spherical conductive particles (B) can be used alone or in combination of two or more.

[0099] The spherical conductive nanoparticles (B) may be surface conductive particles having a structure in which the surface of the conductive particles is coated with a protective agent. The surface-modified conductive particles can ensure the spacing between the conductive particles to suppress aggregation and have excellent dispersibility in an organic solvent.

[0100] As the conductive material constituting the spherical conductive particles (B), there can be mentioned conductive metals, metal oxides, non-conductors with metal coating on the surface, and semiconductor particles, for example, the examples exemplified and explained as the metals and metal oxides constituting the conductive nanoparticles (A) mentioned above. As the conductive material, it is preferred to include the same conductive material as the conductive nanoparticles (A) from the viewpoint of further improving the bonding strength, and more preferably silver particles.

[0101] The protective agent is not particularly limited, and examples thereof include known or commonly used protective agents that can be used as protective agents (stabilizers) for conductive particles. Examples of the protective agent include protective agents having functional groups such as carboxyl, hydroxyl, carbonyl, amide, ether, amino, sulfonic, sulfonyl, sulfinic, sulfenic, mercapto, phosphoric, and phosphite groups. The protective agent may be used alone or in combination of two or more.

[0102] The average particle size (median particle size) of the spherical conductive particles (B) is 0.5 to 1 μm, preferably 0.6 to 0.9 μm. The above average particle size can be measured by a laser diffraction / scattering method. When two or more spherical conductive particles (B) are included, the above average particle size refers to the average particle size of all spherical conductive particles (B).

[0103] (Flat conductive small piece (C))

[0104] When the flat conductive flakes (C) and conductive nanoparticles (A) are combined, the flat conductive flakes (C) themselves are sintered, and the necks between the conductive particles become thicker, so that a stronger sintered body can be obtained. The flat conductive flakes (C) can be used alone or in combination of two or more.

[0105] The flat conductive small pieces (C) may be surface-modified conductive small pieces having a structure in which the surface of the metal small pieces is coated with a protective agent. The surface-modified conductive small pieces can ensure the spacing between the conductive small pieces to suppress aggregation and have excellent dispersibility in an organic solvent.

[0106] As the conductive material constituting the flat conductive flakes (C), there can be mentioned conductive metals, metal oxides, non-conductors with metal coating on the surface, and semiconductor flat particles, for example, the examples exemplified and explained above as the conductive material constituting the conductive nanoparticles (A). As the conductive material, it is preferred to contain the same metal as the conductive nanoparticles (A) from the viewpoint of further improving the bonding strength, and silver particles are more preferred.

[0107] The protective agent is not particularly limited, and examples thereof include known or commonly used organic protective agents that can be used as protective agents (stabilizers) for conductive particles. Examples of the protective agent include organic protective agents having functional groups such as carboxyl, hydroxyl, carbonyl, amide, ether, amino, sulfonic, sulfonyl, sulfinic acid, sulfenic acid, mercapto, phosphoric acid, and phosphite. The protective agent may be used alone or in combination of two or more.

[0108] The average particle size (median particle size) of the flat conductive small pieces (C) is 1 to 10 μm, preferably 2 to 5 μm. The above average particle size can be measured by a laser diffraction / scattering method. When two or more flat conductive small pieces (C) are included, the above average particle size refers to the average particle size of all flat conductive small pieces (C).

[0109] The content of the conductive nanoparticles (A) in 100% by mass of the conductive particles contained in the above-mentioned bonding conductor paste is preferably 5% by mass or more, and more preferably 10% by mass or more. When the above-mentioned content is 5% by mass or more, a denser conductor wiring and bonding structure can be formed. The above-mentioned content is preferably 50% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less. When the above-mentioned content is 50% by mass or less, the amount of the spherical conductive particles (B) and the flat conductive flakes (C) can be sufficiently mixed.

[0110] In the conductive particles 100% by mass contained in the bonding conductor paste, the content of the spherical conductive particles (B) is preferably 30% by mass or more, more preferably 40% by mass or more, and further preferably greater than 50% by mass. When the above content is 30% by mass or more, it is easier to obtain the effect of mixing the spherical conductive particles (B). The above content is preferably 85% by mass or less, more preferably 80% by mass or less, and further preferably 70% by mass or less. When the above content is 85% by mass or less, the amount of conductive nanoparticles (A) and flat conductive flakes (C) can be sufficiently mixed.

[0111] The content of the flat conductive flakes (C) in 100% by mass of the conductive particles contained in the bonding conductor paste is preferably 10% by mass or more, more preferably 15% by mass or more. When the content is 10% by mass or more, it is easier to obtain the effect of adding the flat conductive flakes (C). The content is preferably 65% ​​by mass or less, more preferably 50% by mass or less, and further preferably 40% by mass or less. When the content is 65% by mass or less, the amount of the conductive nanoparticles (A) and the spherical conductive particles (B) can be sufficiently added.

[0112] The total content of the conductive nanoparticles (A), the spherical conductive particles (B) and the flat conductive flakes (C) relative to the total amount of 100 mass % of the conductive particles contained in the above-mentioned bonding conductor paste is preferably 70 mass % or more, more preferably 80 mass % or more, further preferably 90 mass % or more, and particularly preferably 95 mass % or more. When the above-mentioned content is 70 mass % or more, the dispersibility of the conductive particles is better, and the continuous discharge stability and storage stability are better. In addition, the above-mentioned content can be 99.5 mass % or less, and can be preferably 99 mass % or less.

[0113] (Dispersion Medium)

[0114] The above-mentioned dispersion medium contains a hydroxyl-containing ether solvent. The above-mentioned "hydroxyl-containing ether solvent" can be any compound that has one or more (for example, 1 or 2, preferably 1) hydroxyl groups and ether bonds in the molecule and can be used as a solvent. The bonding conductor paste disclosed herein can be made into a volatile bonding conductor paste that has excellent dispersion stability of the above-mentioned conductive particles and is suitable for printing by containing a hydroxyl-containing ether solvent as a dispersion medium.

[0115] The boiling point (at 1 atm) of the hydroxyl-containing ether solvent is preferably 130°C or higher (eg, 130 to 300°C), more preferably 140 to 280°C, further preferably 150 to 260°C, particularly preferably 160 to 240°C.

[0116] The hydroxyl-containing ether solvent preferably has a vapor pressure at 30° C. of, for example, 0.01 to 10.0 mmHg, more preferably 0.05 to 8.0 mmHg, further preferably 0.1 to 6.0 mmHg, and most preferably 0.3 to 4.0 mmHg, from the viewpoint of having moderate volatility.

[0117] From the viewpoint of making the ink suitable for printing, the above-mentioned hydroxyl-containing ether solvent is preferably used at 25°C and a shear rate of 10s -1 The viscosity at 0.1 to 20 mPa·s is preferred, 0.5 to 10 mPa·s is more preferred, 1 to 9 mPa·s is further preferred, and 3 to 8 mPa·s is particularly preferred.

[0118] As the hydroxyl group-containing ether solvent, for example, a compound represented by the following formula (A) ((poly)alkylene glycol monoalkyl ether) is preferred.

[0119] R a -(OR b ) n -OH(A)

[0120] (Where R a represents an alkyl group, an aryl group or an aralkyl group, R b represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer greater than 1).

[0121] As R in formula (A) a Examples of the alkyl group include a linear or branched alkyl group having 1 to 10 carbon atoms (preferably 1 to 5). Examples of the aryl group include an aryl group having 6 to 10 carbon atoms (for example, phenyl, etc.). Examples of the aralkyl group include a linear or branched alkyl group having 1 to 10 carbon atoms (preferably 1 to 5) substituted with an aryl group having 6 to 10 carbon atoms (for example, benzyl, etc.).

[0122] As R in formula (A) b The alkylene group includes, for example, methylene, methylmethylene, dimethylmethylene, ethylene, propylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, etc. Among them, the alkylene group having 1 to 4 carbon atoms is preferred, the alkylene group having 1 to 3 carbon atoms is particularly preferred, and the alkylene group having 2 to 3 carbon atoms is most preferred.

[0123] n is an integer of 1 or more, for example, an integer of 1 to 8, preferably an integer of 1 to 3, and particularly preferably an integer of 2 to 3.

[0124] The boiling point of the compound represented by formula (A) is, for example, 130° C. or higher (for example, 130 to 310° C.), preferably 170° C. or higher, particularly preferably 200° C. or higher.

[0125] Examples of the compound represented by the formula (A) include ethylene glycol monomethyl ether (boiling point: 124° C.), ethylene glycol monoisopropyl ether (boiling point: 141.8° C.), ethylene glycol monobutyl ether (boiling point: 171.2° C.), ethylene glycol monoisobutyl ether (boiling point: 160.5° C.), ethylene glycol monohexyl ether (boiling point: 208° C.), ethylene glycol mono-2-ethylhexyl ether (boiling point: 229° C.), ethylene glycol monophenyl ether (boiling point: 244.7° C.), ethylene glycol monobenzyl ether (boiling point: 256° C.), diethylene glycol monomethyl ether (boiling point: 194° C.), diethylene glycol monobutyl ether (=butyl carbitol, boiling point: 230° C.), diethylene glycol monoisobutyl ether (boiling point: 220° C.), di ... diethylene glycol monoisopropyl ether (boiling point: 207° C.), diethylene glycol monopentyl ether (boiling point: 162° C.), diethylene glycol monoisopentyl ether, diethylene glycol monohexyl ether (= hexyl carbitol, boiling point: 259.1° C.), diethylene glycol mono-2-ethylhexyl ether (boiling point: 272° C.), diethylene glycol monophenyl ether (boiling point: 283° C.), diethylene glycol monobenzyl ether (boiling point: 302° C.), triethylene glycol monomethyl ether (boiling point: 249° C.), triethylene glycol monobutyl ether (boiling point: 271.2° C.), dipropylene glycol monomethyl ether (boiling point: 188° C.), dipropylene glycol n-propyl ether (boiling point: 212° C.), dipropylene glycol n-butyl ether (boiling point: 229° C.), tripropylene glycol methyl ether (boiling point: 242° C.), etc. These solvents may be used alone or in combination of two or more.

[0126] The above-mentioned dispersion medium may include ether solvents other than the above-mentioned hydroxyl-containing ether solvents, ester solvents (for example, (poly)alkylene glycol dialkyl ethers, (poly)alkylene glycol monoalkyl ether monoesters, (poly)alkylene glycol diesters, (poly)alkylene glycol monoesters), terpene solvents, alcohol solvents (excluding hydroxyl-containing ether solvents), urea solvents, aprotic polar solvents, ketone solvents, amine solvents, alkane solvents, etc.

[0127] From the viewpoint of excellent stability during continuous discharge and storage stability and the ability to suppress the generation of pores during sintered body formation, the dispersion medium used in the present disclosure preferably includes an organic solvent (a), an organic solvent (b) and an organic solvent (c). The organic solvent (a), the organic solvent (b) and the organic solvent (c) are different compounds from each other and satisfy the following formulas (1) to (6). Only one kind of the organic solvent (a), the organic solvent (b) and the organic solvent (c) may be used, or two or more kinds may be used.

[0128] 150℃≤Ta≤250℃ (1)

[0129] 150℃≤Tb≤250℃ (2)

[0130] 250℃≤Tc≤350℃ (3)

[0131] δa≥10.0 (4)

[0132] δc≤9.0 (5)

[0133] δc≤δb≤δa (6)

[0134] In the formula, Ta to Tc represent the boiling points of the organic solvents (a) to (c), and δa to δc represent the Hansen solubility parameters of the organic solvents (a) to (c). It should be noted that in this specification, the Hansen solubility parameter is referred to as "SP value" and sometimes expressed as "δ".

[0135] The organic solvents (a) to (c) may be any solvents that can be uniformly dissolved and liquid when mixed in the blending ratio used in the bonding conductor paste, and each may be liquid or solid at room temperature.

[0136] The organic solvent (a) satisfies at least formula (1). That is, the boiling point Ta of the organic solvent (a) satisfies 150°C ≤ Ta ≤ 250°C, preferably 150°C < Ta < 250°C, more preferably 155°C ≤ Ta ≤ 220°C, and further preferably 160°C ≤ Ta ≤ 200°C. By using an organic solvent (a) having a boiling point within the above range, the dispersion medium is easily volatilized during sintering, and a sintered body can be easily formed.

[0137] The organic solvent (a) satisfies at least the formula (4) [δa ≥ 10.0]. The SP value δa of the organic solvent (a) is 10.0 or more, preferably 10.3 or more, and more preferably 10.4 or more within the range satisfying the formula (6). By making the above δa 10.0 or more, the dispersibility of the conductive nanoparticles (A) is excellent, and the separation of the conductive particles and the dispersion medium is not likely to occur. The δa of the organic solvent (a) is, for example, 16.0 or less, and can be 15.0 or less.

[0138] As the organic solvent (a), there can be mentioned: alcohol solvents, urea solvents, aprotic polar solvents, etc., which satisfy the above formulas (1) and (4) and satisfy the formula (6) in the relationship with the organic solvents (b) and (c). As the above alcohol solvent, there can be mentioned compounds having one or more hydroxyl groups, among which tertiary alcohols and hydroxyl-containing ether solvents are preferred. The above alcohol solvent may have two or more hydroxyl groups. As the hydroxyl-containing ether solvent, there can be mentioned (poly)alkylene glycol monoalkyl ethers represented by the above formula (A), alkoxy-substituted alcohols, etc.

[0139] Specific examples of the organic solvent (a) include pinacol (δ10.7, boiling point 172°C), tetramethylurea (δ10.6, boiling point 177°C), 3-methoxybutanol (δ10.6, boiling point 161°C), 1-methylcyclohexanol (δ10.4, boiling point 155°C), methyl carbitol (diethylene glycol monomethyl ether) (δ10.7, boiling point 193°C), etc.

[0140] The organic solvent (b) satisfies at least formula (2). That is, the boiling point Tb of the organic solvent (b) satisfies 150°C≤Tb≤250°C, preferably 150°C<Tb<250°C, more preferably 180°C≤Tb≤248°C, and further preferably 200°C≤Tb≤245°C. By using an organic solvent (b) having a boiling point within the above range, the dispersion medium is easily volatilized during sintering, and a sintered body can be easily formed. In addition, by using an organic solvent (b) having a boiling point below 250°C, the generation of pores during sintering can be suppressed.

[0141] The organic solvent (b) satisfies at least the formula (6). The SP value δb of the organic solvent (b) is preferably 8.0 to 12.0, more preferably 8.5 to 11.0, and further preferably 9.0 to 10.5 within the range satisfying the formula (6). When the above δb is within the above range, the compatibility of the organic solvent (a) and the organic solvent (c) is improved, and they are not easily separated, and there is a tendency for the continuous discharge stability and storage stability to be more excellent.

[0142] As the organic solvent (b), there may be mentioned an organic solvent that satisfies formula (2) among alcohol solvents, ester solvents, ketone solvents, amine solvents, etc., and satisfies formula (6) in relation to organic solvents (a) and (c). As the above-mentioned alcohol solvent, there may be mentioned a solvent compound having one or more hydroxyl groups, among which tertiary alcohols, hydroxyl-containing ether solvents, and ester alcohols are preferred. As the hydroxyl-containing ether solvent, there may be mentioned (poly)alkylene glycol monoalkyl ethers represented by the above-mentioned formula (A), alkoxy-substituted alcohols, etc. Ester alcohols are compounds having an ester bond and a hydroxyl group, and there may be mentioned (poly)alkylene glycol monoalkyl ether monoesters, etc. As the ester solvent, there may be mentioned diacetates of glycols such as (poly)alkylene glycols, etc. As the ketone solvent, cyclic ketones are preferred. As the amine solvent, alkylamines are preferred.

[0143] The organic solvent (b) can be selected on the premise that it satisfies the formula (6) in terms of the relationship with the organic solvents (a) and (c). Specifically, for example, d-Camphor (camphor) (δ10.4, boiling point 204°C), 1-heptanol (δ10.0, boiling point 177°C), butyl carbitol (diethylene glycol monobutyl ether) (δ10.2, boiling point 231°C), ethyl carbitol (diethylene glycol monoethyl ether) (δ10.5, boiling point 196°C), tripropylene glycol monomethyl ether (δ9.4, boiling point 243°C), α-terpineol (δ9.3 , boiling point 220℃), dihydroterpineol (δ9.0, boiling point 210℃), 1,3-butanediol diacetate (δ9.2, boiling point 232℃), propylene glycol diacetate (δ9.3, boiling point 190℃), butyl carbitol acetate (δ9.0, boiling point 247℃), dipropylene glycol butyl ether (δ9.2, boiling point 230℃), isophorone (δ9.5, boiling point 213℃), 1-decanol (δ9.6, boiling point 230℃), propylene glycol monobutyl ether (δ9.0, boiling point 170℃), 1-nonanol (δ9.8, boiling point 214℃), etc.

[0144] The boiling point Tb of the organic solvent (b) is preferably higher than the boiling point Ta of the organic solvent (a), that is, preferably Tb>Ta. The temperature difference [Tb-Ta] between Tb and Ta is preferably 2°C or more, more preferably 5°C or more, and further preferably 10°C or more. When the temperature difference is 2°C or more, the generation of pores during sintering can be further suppressed.

[0145] The organic solvent (c) satisfies at least formula (3). That is, the boiling point Tc of the organic solvent (c) satisfies 250°C ≤ Tc ≤ 350°C, preferably satisfies 250°C < Tc < 350°C, more preferably satisfies 250°C < Tc ≤ 320°C, and further preferably satisfies 250°C < Tc ≤ 300°C. By using an organic solvent (c) having a boiling point within the above range, rapid volatilization of the organic solvent (a) and the organic solvent (b) during sintering can be suppressed, thereby suppressing the generation of pores.

[0146] The organic solvent (c) at least satisfies the formula (5) [δc≤9.0]. The SP value δc of the organic solvent (c) is 9.0 or less, preferably 8.7 or less, and more preferably 8.5 or less. By making the above δ 9.0 or less, the generation of pores during sintering can be suppressed. The δc of the organic solvent (c) is, for example, 6.0 or more, and can be 7.0 or more.

[0147] As the organic solvent (c), there can be mentioned ether solvents, alkane solvents, ester solvents, etc., which satisfy the above formulas (3) and (5) and satisfy the formula (6) in the relationship with the organic solvents (a) and (b). As the ether solvent, there can be mentioned (poly) alkylene glycol dialkyl ethers, etc. As the alkane solvent, an alkane having 14 or more carbon atoms (e.g., 14 to 20 carbon atoms) is preferred. As the ester solvent, there can be mentioned esters of (poly) alkylene glycol alkyl ethers and fatty acids.

[0148] Specific examples of the organic solvent (c) include dibutyl carbitol (diethylene glycol dibutyl ether) (δ 8.3, boiling point 255° C.), tetradecane (δ 7.9, boiling point 254° C.), and hexadecane (δ 8.0, boiling point 287° C.).

[0149] The boiling point Tc of the organic solvent (c) is preferably higher than the boiling point Tb of the organic solvent (b), that is, preferably Tc>Tb. The temperature difference [Tc-Tb] between Tc and Tb is preferably 2°C or more, more preferably 6°C or more, and further preferably 10°C or more. When the temperature difference is 2°C or more, the generation of pores during sintering can be further suppressed.

[0150] The boiling point Tc of the organic solvent (c) is preferably higher than the boiling point Ta of the organic solvent (a), that is, preferably Tc>Ta. The temperature difference between Tc and Ta [Tc-Ta] is preferably 30°C or more, more preferably 50°C or more, and further preferably 60°C or more. When the temperature difference is 30°C or more, the generation of pores during sintering can be further suppressed.

[0151] The SP value δa of the organic solvent (a), the SP value δb of the organic solvent (b), and the SP value δc of the organic solvent (c) have a relationship satisfying the above formula (6) [δc≤δb≤δa]. Among them, δb is preferably higher than δc, that is, preferably satisfies δc<δb. In addition, δa is preferably higher than δb, that is, preferably satisfies δb<δa.

[0152] The difference between δb and δc [δb-δc] is preferably 0.1 or more, more preferably 0.2 or more, and further preferably 0.5 or more. When the above difference is 0.1 or more, the dispersibility of the conductive particles is more excellent, and the continuous discharge stability is more excellent. The above difference is preferably 2.0 or less, more preferably 1.5 or less, and further preferably 1.3 or less. When the above difference is 2.0 or less, the conductive particles are not easily separated from the dispersion medium, and the continuous discharge stability and storage stability are more excellent.

[0153] The difference between δa and δb [δa-δb] is preferably 0.1 or more, more preferably 0.2 or more, and further preferably 0.5 or more. When the difference is 0.1 or more, the dispersibility of the conductive particles is more excellent, and the continuous discharge stability is more excellent. The difference is preferably 2.5 or less, more preferably 2.0 or less, and further preferably 1.8 or less. When the difference is 2.5 or less, the conductive particles are not easily separated from the dispersion medium, and the continuous discharge stability and storage stability are more excellent.

[0154] Based on formula (4) and formula (5), the difference between δa and δc [δa-δc] is 1.0 or more, preferably 1.5 or more, and more preferably 2.0 or more. When the above difference is 1.0 or more, the generation of pores during sintering can be further suppressed. The above difference is preferably 5.0 or less, more preferably 4.0 or less, and further preferably 3.0 or less. When the above difference is 5.0 or less, the conductive particles are not easily separated from the dispersion medium, and the continuous discharge stability and storage stability are more excellent.

[0155] The ratio of the organic solvent (a) to the total amount of the organic solvent (a), the organic solvent (b) and the organic solvent (c) (100% by mass) [organic solvent (a) / {organic solvent (a)+organic solvent (b)+organic solvent (c)}] is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and still more preferably 15 to 50% by mass. When the ratio is within the above range, the dispersion medium is easily volatilized during sintering, a sintered body can be easily formed, and the dispersibility of the metal particles is more excellent.

[0156] The ratio of the organic solvent (b) to the total amount of the organic solvent (a), the organic solvent (b) and the organic solvent (c) (100% by mass) [organic solvent (b) / {organic solvent (a)+organic solvent (b)+organic solvent (c)}] is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and still more preferably 15 to 50% by mass. When the ratio is within the above range, the compatibility of the organic solvents is excellent, and the continuous discharge stability and storage stability are further excellent.

[0157] The ratio of the organic solvent (c) to the total amount of the organic solvent (a), the organic solvent (b) and the organic solvent (c) (100% by mass) [organic solvent (c) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is preferably 5 to 70% by mass, more preferably 10 to 60% by mass, and still more preferably 15 to 50% by mass. When the ratio is within the above range, the generation of pores during sintering can be further suppressed.

[0158] The content of the organic solvent (c) is preferably 20 to 400 parts by mass, more preferably 30 to 300 parts by mass, and even more preferably 50 to 200 parts by mass relative to 100 parts by mass of the organic solvent (a). When the content is within the above range, the balance of the blending amounts of the organic solvent (a) and the organic solvent (c) is good, and the pore suppression during sintering and the dispersibility of the metal particles are further improved.

[0159] The content of the organic solvent (b) is preferably 10 to 200 parts by mass, more preferably 20 to 150 parts by mass, and even more preferably 40 to 100 parts by mass relative to 100 parts by mass of the total amount of the organic solvent (a) and the organic solvent (c). When the content is within the above range, the compatibility of the organic solvent (a) and the organic solvent (c) is further improved, and the continuous discharge stability and low-temperature storage property are more excellent.

[0160] The above-mentioned dispersion medium may also contain other solvents (organic solvents) other than organic solvent (a), organic solvent (b) and organic solvent (c). Relative to the total amount of 100% by mass of the above-mentioned dispersion medium, the total content of organic solvent (a), organic solvent (b) and organic solvent (c) in the above-mentioned dispersion medium is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. When the above-mentioned content ratio is 50% by mass or more, the dispersibility of the conductive particles and the compatibility of each organic solvent are more excellent, and the continuous discharge stability, storage stability and pore formation inhibition during sintering are more excellent.

[0161] When the organic solvent (a), the organic solvent (b) and the organic solvent (c) are mixed in the mixing ratio used in the bonding conductor paste, the organic solvent (a), the organic solvent (b) and the organic solvent (c) preferably dissolve uniformly at room temperature without phase separation. In addition, in the bonding conductor paste, the organic solvent (a), the organic solvent (b) and the organic solvent (c) preferably dissolve uniformly at room temperature without phase separation. In particular, it is preferred that the organic solvent (a), the organic solvent (b) and the organic solvent (c) do not phase separate at 22 to 28° C. (preferably 10 to 30° C., more preferably 0 to 35° C.).

[0162] From the viewpoint of the dispersion stability of the conductive particles and the volatility of the dispersion medium during sintering, the content of the hydroxyl-containing ether solvent in the total amount (100% by mass) of the dispersion medium is preferably 10 to 60% by mass, more preferably 15 to 55% by mass, and still more preferably 25 to 45% by mass. The content ratio of the hydroxyl-containing ether solvent in the total amount (100% by mass) of the organic solvent (a), the organic solvent (b), and the organic solvent (c) in the bonding conductor paste is preferably within the above range. In addition, it is also preferred that the dispersion medium is composed of only the hydroxyl-containing ether solvent (100% by mass).

[0163] The content of the hydroxyl-containing ether solvent is preferably 1 to 15 parts by mass, more preferably 1.5 to 12 parts by mass, and even more preferably 2 to 10 parts by mass relative to 100 parts by mass of the conductive particles. When the content is within the above range, the conductive particles have excellent dispersion stability and volatility during sintering.

[0164] The content of the dispersion medium is preferably 4 to 20 parts by mass, more preferably 5 to 15 parts by mass, and even more preferably 6 to 12 parts by mass relative to 100 parts by mass of the conductive particles. When the content is within the above range, the conductive particles have excellent dispersion stability and volatility during sintering.

[0165] The total content ratio of the organic solvent (a), the organic solvent (b), and the organic solvent (c) relative to 100 parts by mass of the conductive particles is preferably within the above range.

[0166] (Urea compounds)

[0167] The bonding conductor paste disclosed herein contains a urea compound as an essential component. The bonding conductor paste disclosed herein can suppress solvent bleed-out by containing the urea compound, and can improve printing suitability when forming a sintered body such as a conductor wiring and a bonding structure for connecting electronic components. In addition, the generation of voids during the formation of the sintered body can be suppressed, and a sintered body such as a conductor wiring and a bonding structure having high bonding strength and an electronic device having the same can be produced.

[0168] The urea compound is preferably a rheology control agent having a urea group (urea rheology control agent), and examples thereof include: modified urea, urea-modified carbamate, polymer urea derivatives and other modified ureas, and urea-modified medium-polar polyamides, urea-modified low-polar polyamides and other urea-modified polyamides. It can be considered that the urea compound forms a three-dimensional network structure in the bonding conductor paste containing the hydroxyl-containing ether solvent dispersed with the conductive particles through the strong polar hydrogen bonding force and association effect of the urea group, and appropriately increases the viscosity, thereby inhibiting solvent exudation, preventing solvent boiling and inhibiting the generation of pores. From the viewpoint of more efficiently inhibiting solvent exudation and the generation of pores, modified urea, urea-modified carbamate, and urea-modified polyamide are preferred. These urea compounds can be used alone or in combination of two or more.

[0169] Examples of modified ureas include compounds obtained by introducing copolymerization or substituents into a main chain having one or more urea groups; examples of urea-modified carbamates include compounds in which a portion of the main chain having one or more urea groups is a polyurethane chain; examples of urea-modified polyamides include compounds in which a portion of the main chain having one or more urea groups is an amide chain.

[0170] Examples of the polymer urea derivative include urea derivatives having one or more urea groups and having a polystyrene-equivalent number average molecular weight of 1000 to 70000 by GPC. Among them, compounds having two or more urea groups and having a polystyrene-equivalent number average molecular weight of 3000 to 70000 by GPC are preferred.

[0171] Regarding the above-mentioned urea compound, if it is easy to stably form a three-dimensional network structure and the dispersibility is improved, it is preferably mixed with a solvent in advance to prepare a mixture with the above-mentioned urea compound. If further consideration is taken, the solvent is preferably selected from pyrrolidone derivatives, polyalkylene glycols, aliphatic alcohols, aromatic alcohols, glycol ethers, and hydrocarbon solvents, more preferably selected from pyrrolidone derivatives, polyalkylene glycols, amide ethers, and amide esters, and most preferably pyrrolidone derivatives.

[0172] In addition, when a specific solvent is used as a main solvent for each urea compound, each urea compound can easily form a three-dimensional network structure stably, and the dispersibility can be easily improved.

[0173] Therefore, when using modified urea, if the dispersibility is improved, it is preferred to use a pyrrolidone derivative. Examples of pyrrolidone derivatives include N-methylpyrrolidone, N-ethylpyrrolidone, N-vinylpyrrolidone, and 2-pyrrolidone. If the dispersibility is further improved, it is preferred to use N-methylpyrrolidone.

[0174] When urea-modified urethane is used, polyalkylene glycol is also preferably used. Examples of the polyalkylene glycol include polyethylene glycol and polypropylene glycol. In view of the improvement of dispersibility, polypropylene glycol is preferably used.

[0175] When urea-modified polyamide is used, it is also preferred to select from aliphatic alcohols, glycol ethers, and hydrocarbon solvents. As aliphatic alcohols, methanol, ethanol, 1-propanol, 2-propanol, isopropanol, isobutyl alcohol, tert-butyl alcohol, etc. can be cited; as glycol ethers, ethylene glycol monophenyl ether (monophenyl glycol), propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethylene glycol dimethyl ether, 3-methoxybutanol, 3-methoxy-3-methylbutanol, etc. can be cited; as hydrocarbon solvents, benzene, toluene, xylene, solvent naphtha, octane, mineral spirits, etc. can be cited; if further consideration is given to improving dispersibility, it is preferred to select from isopropanol, isobutyl alcohol, ethylene glycol monophenyl ether (monophenyl glycol), propylene glycol monomethyl ether, solvent naphtha, and mineral spirits; if further consideration is given, it is preferred to use isopropanol, ethylene glycol monophenyl ether (monophenyl glycol), and solvent naphtha.

[0176] As the above-mentioned modified urea, urea-modified urethane, and urea-modified polyamide, commercially available products can be used, and specific examples include: BYK-410 (main component: modified urea), BYK-411 (main component: modified urea), BYK-415 (main component: polymer urea derivative), BYK-420 (main component: modified urea), BYK-425 (main component: urea-modified urethane), BYK-430 (main component: urea-modified medium-polar polyamide), BYK-431 (main component: urea-modified low-polar polyamide), BYK-7420 (main component: modified urea), etc., all manufactured by BYK Japan Co., Ltd.

[0177] The content of the urea compound is preferably 3 to 50 parts by mass, more preferably 3.5 to 30 parts by mass, and further preferably 4 to 20 parts by mass relative to 100 parts by mass of the ether solvent containing the hydroxyl group. It is believed that by making the above-mentioned content ratio 3 parts by mass or more, a three-dimensional network structure can be formed in the above-mentioned bonding conductor paste to appropriately increase the viscosity, thereby inhibiting solvent exudation and improving printing suitability. In addition, it is believed that by making the above-mentioned content ratio 50 parts by mass or less, the sintering hindrance caused by the urea compound remaining in the form of coating the entire silver particles can be inhibited, thereby showing high bonding strength. Therefore, when the above-mentioned content ratio is within the above-mentioned range, solvent exudation can be inhibited, and the printing suitability when forming a sintered body such as a conductor wiring, a bonding structure, etc. for connecting electronic components can be improved. In addition, the generation of pores during the formation of the sintered body can be inhibited, and a sintered body of a conductor wiring, a bonding structure, etc. with high bonding strength and an electronic device having them can be produced.

[0178] The content of the urea compound is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and further preferably 3 to 12 parts by mass relative to 100 parts by mass of the dispersion medium containing the ether solvent containing a hydroxyl group. It is believed that by making the above-mentioned content ratio 1 part by mass or more, a three-dimensional network structure can be formed in the above-mentioned bonding conductor paste to appropriately increase the viscosity, thereby inhibiting solvent exudation and improving printing suitability. In addition, it is believed that by making the above-mentioned content ratio 20 parts by mass or less, the sintering hindrance caused by the urea compound remaining in the form of coating the entire silver particles can be inhibited, thereby showing high bonding strength. Therefore, when the above-mentioned content ratio is within the above-mentioned range, solvent exudation can be inhibited, and the printing suitability when forming a sintered body such as a conductor wiring, a bonding structure, etc. for connecting electronic components can be improved. In addition, the generation of pores during the formation of the sintered body can be suppressed, and a sintered body of a conductor wiring, a bonding structure, etc. with high bonding strength and an electronic device having them can be produced. The content of the urea compound relative to 100 parts by mass of the total of the organic solvent (a), the organic solvent (b), and the organic solvent (c) in the bonding conductor paste is preferably within the above range.

[0179] The content of the urea compound is preferably 0.1 to 2 parts by mass, more preferably 0.2 to 1.5 parts by mass, and further preferably 0.3 to 1.2 parts by mass relative to 100 parts by mass of the conductive particles. It is believed that by making the content ratio 0.1 parts by mass or more, a three-dimensional network structure can be formed in the bonding conductor paste to appropriately increase the viscosity, thereby inhibiting solvent oozing out and improving printing suitability. In addition, it is believed that by making the content ratio 2 parts by mass or less, the sintering hindrance caused by the urea compound remaining in the form of coating the entire silver particles can be inhibited, thereby showing high bonding strength. Therefore, when the content ratio is within the above range, solvent oozing out can be inhibited, and the printing suitability when forming a sintered body such as a conductor wiring, a bonding structure, etc. for connecting electronic components can be improved. In addition, the generation of pores during the formation of the sintered body can be inhibited, and a sintered body of a conductor wiring, a bonding structure, etc. with high bonding strength and an electronic device having them can be produced. The content of the urea compound relative to 100 parts by mass of the total of the organic solvent (a), the organic solvent (b), and the organic solvent (c) in the bonding conductor paste is preferably within the above range.

[0180] The content of the urea compound is preferably 0.09 to 1.8 parts by mass, more preferably 0.15 to 1.4 parts by mass, and further preferably 0.25 to 1.1 parts by mass relative to the total of 100 parts by mass of the conductive particles and the dispersion medium. It is believed that by making the above-mentioned content ratio 0.09 parts by mass or more, a three-dimensional network structure can be formed in the above-mentioned bonding conductor paste to appropriately increase the viscosity, thereby inhibiting solvent exudation and improving printing suitability. In addition, it is believed that by making the above-mentioned content ratio 1.8 parts by mass or less, the sintering hindrance caused by the urea compound remaining in the form of coating the entire silver particles can be inhibited, thereby showing high bonding strength. Therefore, when the above-mentioned content ratio is within the above-mentioned range, solvent exudation can be inhibited, and the printing suitability when forming a sintered body such as a conductor wiring, a bonding structure, etc. for connecting electronic components can be improved. In addition, the generation of pores during the formation of the sintered body can be inhibited, and a sintered body of a conductor wiring, a bonding structure, etc. with high bonding strength and an electronic device having them can be produced.

[0181] (bonding conductor paste)

[0182] The content of the conductive particles in the bonding conductor paste is preferably 70 to 99.5% by mass, more preferably 80 to 98% by mass, and even more preferably 85 to 95% by mass, relative to the total amount of the bonding conductor paste (100% by mass). When the content is within the above range, the dispersibility of the conductive particles is better, and the continuous discharge stability and storage stability are better. In addition, the total content of the conductive nanoparticles (A), the spherical conductive particles (B), and the flat conductive flakes (C) in the bonding conductor paste is preferably within the above range.

[0183] The content of the dispersion medium (particularly the organic solvent) in the bonding conductor paste is preferably 0.5 to 30% by mass, more preferably 2 to 20% by mass, and even more preferably 5 to 15% by mass, relative to 100% by mass of the total amount of the bonding conductor paste. When the content is within the above range, the dispersibility of the conductive particles is further improved. The total content of the organic solvent (a), the organic solvent (b), and the organic solvent (c) in the bonding conductor paste is preferably within the above range.

[0184] The content of the hydroxyl-containing ether solvent in the bonding conductor paste is preferably 0.5 to 15% by mass, more preferably 1 to 13% by mass, and even more preferably 2 to 12% by mass, relative to 100% by mass of the total amount of the bonding conductor paste. When the content is within the above range, the dispersibility of the conductive particles and the volatility during sintering are more excellent.

[0185] The total content of the conductive particles and the dispersion medium in the bonding conductor paste is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more, relative to 100% by mass of the total amount of the bonding conductor paste.

[0186] The content of the urea compound in the bonding conductor paste is preferably 0.09-1.8% by mass, more preferably 0.15-1.4% by mass, and further preferably 0.25-1.1% by mass, relative to the total amount of the bonding conductor paste (100% by mass). It is believed that by making the content ratio preferably 0.09% by mass or more, a three-dimensional network structure can be formed in the bonding conductor paste to appropriately increase the viscosity, thereby inhibiting solvent exudation and improving printing suitability. In addition, it is believed that by making the content ratio 1.8% by mass or less, the sintering hindrance caused by the urea compound remaining in the form of coating the entire silver particles can be inhibited, thereby showing high bonding strength. Therefore, when the content ratio is within the above range, solvent exudation can be inhibited, and the printing suitability when forming a sintered body such as a conductor wiring, a bonding structure, etc. for connecting electronic components can be improved. In addition, the generation of pores during the formation of the sintered body can be inhibited, and a sintered body such as a conductor wiring, a bonding structure, etc. with high bonding strength and an electronic device having them can be produced.

[0187] The bonding conductor paste may also contain other components in addition to the metal particles, the dispersion medium and the urea compound. The bonding conductor paste may contain, for example, an adhesive and an additive (for example, a polymer compound with a molecular weight of 10,000 or more, such as an epoxy resin, a silicone resin, an acrylic resin, etc.). The content ratio thereof relative to the total amount of 100 mass % of the bonding conductor paste is, for example, 10 mass % or less, preferably 5 mass % or less, more preferably 3 mass % or less, and particularly preferably 1 mass % or less. Therefore, according to the bonding conductor paste, the non-conductive component derived from the polymer compound can form a conductor wiring and a bonding structure with excellent conductivity [resistance value, for example, 10×10 -6 Ω·cm or less, preferably 9.0×10 -6 Ω·cm or less, more preferably 8.5×10 -6 Ω·cm or less, more preferably 7.0×10 -6 Ω·cm or less].

[0188] It is believed that the bonding conductor paste of the present disclosure can form a three-dimensional network structure in the bonding conductor paste by including a urea compound as a rheology control agent, thereby appropriately increasing the viscosity, thereby inhibiting solvent exudation, promoting solvent volatilization, and inhibiting the generation of pores. Therefore, it is possible to inhibit solvent exudation and improve the printing suitability when forming a sintered body such as a conductor wiring and a bonding structure for connecting electronic components. In addition, the generation of pores during the formation of the sintered body can be inhibited, and a sintered body such as a conductor wiring and a bonding structure with high bonding strength and an electronic device having the same can be produced.

[0189] (Sintered body)

[0190] The bonding conductor paste of the present disclosure is applied to a substrate by a printing method (specifically, a dispenser printing method, a mask printing method, a screen printing method, an inkjet printing method, etc.), and then sintered to form a sintered body, thereby forming a conductor wiring and a bonding structure. Among them, the bonding conductor paste is preferably printed by a dispenser printing method from the viewpoint of excellent continuous discharge stability.

[0191] The sintering temperature is, for example, 150° C. or higher and lower than 300° C., and preferably 170 to 250° C. The sintering time is, for example, 0.1 to 2 hours, and preferably 0.5 to 1 hour.

[0192] The sintering may be performed in any gas atmosphere such as air, nitrogen, or argon. However, it is preferably performed in air from the viewpoint of being economical and providing a conductor wiring or a junction structure having a lower resistance value.

[0193] The thickness of the bonding conductor paste applied on the substrate and the conductor wiring or the bonded structure formed by the above method is, for example, in the range of 15 to 400 μm, preferably 20 to 250 μm, and more preferably 40 to 200 μm.

[0194] As the substrate for forming the conductor wiring and the joint structure, for example, there can be cited: a ceramic substrate, a SiC substrate, a gallium nitride substrate, a metal substrate, a glass epoxy substrate, a BT resin substrate, a glass substrate, a resin substrate, etc. The shape of the conductor wiring and the joint structure is not particularly limited as long as it can connect electronic components.

[0195] The sintered body (e.g., conductor wiring, bonding structure) formed on the substrate using the above-mentioned bonding conductor paste is sintered to tightly aggregate the conductive particles, and the conductive particles are fused with each other, thereby being able to exert excellent bonding strength to the substrate. For example, the bonding strength when a silver-plated copper substrate is bonded to a silver-plated Si chip (according to JIS Z3198) is preferably 30 MPa or more, more preferably 40 MPa or more.

[0196] The porosity measured by an ultrasonic imaging device (SAT) in a sintered body (e.g., conductor wiring, joint structure) formed on a substrate using the above-mentioned bonding conductor paste is preferably 30% or less, more preferably 15% or less, and further preferably less than 8%. When the above-mentioned porosity is 30% or less, the bonding strength is further increased. It can be considered that a high porosity means that there are many voids in the bonding interface, etc., and the heat transfer area with the bonded part in the bonded body is reduced. When the semiconductor is working, a narrow heat transfer area is fatal in terms of heat dissipation, and the possibility of generating hot spots and causing failures increases. The above-mentioned porosity can be specifically measured by the method described in the examples.

[0197] Since the bonding conductor paste has the above-mentioned properties, it can be preferably used for the purpose of manufacturing electronic components (for example, power semiconductor modules, LED modules, etc.) using a printing method, for example.

[0198] Each method disclosed in this specification may also be combined with any other features disclosed in this specification. Each configuration and their combination in each embodiment is an example, and the addition, omission, substitution and other changes of the configuration may be appropriately made within the scope of the main purpose of the present disclosure. In addition, each invention disclosed in this disclosure is not limited to the embodiment and the following examples, but only to the claims.

[0199] Example

[0200] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.

[0201] (Average particle size of conductive nanoparticles (A))

[0202] Next, the average particle size (median particle size) of the conductive nanoparticles (A) was measured by the following method.

[0203] The suspension containing surface-modified silver nanoparticles prepared in Preparation Example 1 was observed using a transmission electron microscope. The observation was set to 100,000 times and 4 fields of view × 50. In addition, the observation site was set to the site where large and small particles coexisted. By analyzing the image, the number particle size distribution was obtained. For this number particle size distribution, a conversion to a volume particle size distribution was performed using a known conversion formula and assuming that the particles had an aspect ratio of 1. The average particle size (median particle size) was obtained based on the particle size distribution as the average particle size of the conductive nanoparticles (A).

[0204] (Average particle size of spherical conductive particles (B) and flat conductive flakes (C))

[0205] It is a value measured by the laser diffraction / scattering method.

[0206] The metal particles, solvent, and urea compound used are as follows.

[0207] [Metal particles]

[0208] Surface modified silver nanoparticles (Preparation Example 1): average particle size (median particle size) 50 nm

[0209] AG-2-8F: Trade name "AG-2-8F", manufactured by DOWA ELECTRONICS MATERIALS, spherical silver particles, average particle size (median particle size) 0.8 μm

[0210] 41-104: Trade name "41-104", manufactured by Technic, flat silver flakes, average particle size (median particle size) 3.3 μm

[0211] [Solvent (I): Highly polar solvent]

[0212] ·TMU: Tetramethylurea, δ10.6, boiling point 177°C, manufactured by Daicel Co., Ltd.

[0213] [Solvent (II): medium polar solvent]

[0214] ·TPM: Tripropylene glycol monomethyl ether, δ 9.4, boiling point 243°C, manufactured by ANDOH PARACHEMIE

[0215] DHTP: dihydroterpineol, δ 9.0, boiling point 210°C, manufactured by YASUHARA CHEMICAL

[0216] [Solvent (III): Low polarity solvent]

[0217] ·DBC: Dibutyl carbitol, δ8.3, boiling point 255°C, manufactured by Tokyo Chemical Industry Co., Ltd.

[0218] [Urea compounds]

[0219] BYK-430: Trade name "BYK-430", manufactured by BYK Japan Co., Ltd. Main component: urea-modified medium-polar polyamide

[0220] BYK-420: Trade name "BYK-420", manufactured by BYK Japan Co., Ltd. Main component: modified urea

[0221] Preparation Example 1 (Preparation of surface-modified silver nanoparticles)

[0222] Silver oxalate (molecular weight: 303.78) was obtained from silver nitrate (manufactured by Wako Pure Chemical Industries, Ltd.) and oxalic acid dihydrate (manufactured by Wako Pure Chemical Industries, Ltd.).

[0223] 40.0 g (0.1317 mol) of the above silver oxalate was placed in a 500 mL flask, and 60 g of n-butanol was added thereto to prepare a n-butanol slurry of silver oxalate.

[0224] To the obtained slurry was added dropwise an amine mixture of 115.58 g (1.5802 mol) of n-butylamine (molecular weight: 73.14, reagent manufactured by Tokyo Chemical Industry Co., Ltd.), 51.06 g (0.3950 mol) of 2-ethylhexylamine (molecular weight: 129.25, reagent manufactured by Wako Pure Chemical Industries, Ltd.) and 17.02 g (0.1317 mol) of n-octylamine (molecular weight: 129.25, reagent manufactured by Tokyo Chemical Industry Co., Ltd.) at 30°C.

[0225] After the dropwise addition, the mixture was stirred at 30° C. for 1 hour to allow the complex reaction of silver oxalate and amine to proceed.

[0226] After the silver oxalate-amine complex was formed, the silver oxalate-amine complex was thermally decomposed by heating at 110° C. for 1 hour to obtain a dark blue suspension containing surface-modified silver nanoparticles.

[0227] The obtained suspension was cooled, and 120 g of methanol (a reagent manufactured by Wako Pure Chemical Industries, Ltd., special grade) was added thereto for stirring, and then the surface-modified silver nanoparticles were precipitated by centrifugation, and the supernatant was removed. Next, 120 g of dibutyl carbitol was added for stirring, and then the surface-modified silver nanoparticles were precipitated by centrifugation, and the supernatant was removed. Thus, surface-modified silver nanoparticles in a wet state containing dibutyl carbitol were obtained. According to the measurement results of a thermogravimetric analysis balance using TG / DTA6300 manufactured by SII, the content of the surface-modified silver nanoparticles in the total amount (100 wt%) of the surface-modified silver nanoparticles in a wet state was 81.6 wt%. That is, the surface-modified silver nanoparticles in a wet state contained 18.4 wt% of dibutyl carbitol.

[0228] In addition, the surface-modified silver nanoparticles in a wet state were observed using a scanning electron microscope (JESL Co., Ltd., JSM-6700F), and the particle sizes of 10 silver nanoparticles randomly selected in the SEM photograph were obtained, and their average value was taken as the average particle size. The average particle size (primary particle size) of the silver nanoparticle part in the surface-modified silver nanoparticles was 50 nm.

[0229] Example 1 (Preparation of bonding conductor paste)

[0230] Trade name "41-104" (25.50 g), AG-2-8F (59.50 g), tetramethyl urea (3.40 g), tripropylene glycol methyl ether (3.40 g) and BYK-420 (0.6 g) were added and mixed with an autorotating and orbiting stirrer (manufactured by THINKY Co., Ltd., ARE-310) to prepare Liquid A.

[0231] 92.40 g of Liquid A was added to 18.40 g of the wet surface-modified silver nanoparticles (containing 18.4% by mass of dibutyl carbitol) obtained in Preparation Example 1, and mixed using an autorotating and orbiting stirrer (ARE-310 manufactured by THINKY Corporation) to obtain a gray-black bonding conductor paste (1).

[0232] Examples 2 to 6, Comparative Examples 1 to 4

[0233] A bonding conductor paste was prepared in the same manner as in Example 1 except that the formulation was changed as shown in Table 1. The numerical values ​​of the components shown in Table 1 represent "parts by mass".

[0234] <Evaluation>

[0235] The following evaluations were performed on the bonding conductor pastes obtained in Examples and Comparative Examples.

[0236] The substrates and equipment used are as follows.

[0237] [Substrate]

[0238] ·Silver-plated substrate (manufactured by Nippon Testpanel Co., Ltd.)

[0239] Substrate: Copper (1.0mm×9mm×60mm)

[0240] Substrate: Chemical nickel plating (5μm)

[0241] Top surface: Semi-gloss silver plating (1.0μm)

[0242] Silicon chip (manufactured by YAMANAKA HUTECH Co., Ltd.)

[0243] Silicon (0.525mm×3mm×3mm)

[0244] Substrate: Titanium 500nm sputtered

[0245] Surface: Silver 2μm sputtering

[0246] [equipment]

[0247] ·Sintering furnace (reflow furnace)

[0248] RSS-450-210-FA (manufactured by UNITEMP)

[0249] (1) Printing evaluation

[0250] The bonding conductor paste obtained in the above-mentioned Examples and Comparative Examples was printed on the above-mentioned substrate via a metal mask having 3×3 openings of 5×5 mm arranged at intervals of 2.5 mm.

[0251] The printability was evaluated based on the following criteria. The results are shown in Table 1.

[0252] ·On ​​the silver-plated substrate, the shape of the bonding conductor paste printed in the opening of 5×5 mm was maintained, and the dispersion medium did not ooze out of the paste···○ (good)

[0253] · On the silver-plated substrate, the shape of the bonding conductor paste printed in the 5×5 mm opening was collapsed, or the dispersion medium oozed out of the paste···× (defective)

[0254] (2) Chip shear strength

[0255] Next, using the above-mentioned reflow furnace, a material obtained by placing a substrate (2) identical to the substrate (1) on the formed coating film was heated and sintered under the following conditions without applying pressure to produce a sample (substrate (1) / sintered bonding conductor paste / substrate (2)).

[0256] ·Under atmosphere:

[0257] 25℃→200℃(heating rate: 5℃ / min)

[0258] Keep at 200℃ for 60min

[0259] For the obtained samples (n=4), the bonding strength between the substrate (1) and the substrate (2) was measured under the following conditions at room temperature using a die shear tester SERIES 4000 (manufactured by DAGE), and the bonding properties were evaluated.

[0260] Table 1 shows the average values ​​of the bonding strength (MPa) when the silver-plated substrate and the silicon chip were used.

[0261] Test speed: 50μm / s

[0262] Test height: 50μm

[0263] (3) SAT evaluation

[0264] For the samples made in the evaluation of chip shear strength, the peeling state of the bonding interface was observed with a probe using an ultrasonic imaging device and a 25MHz reflection method. The image of the observation result was divided into 100 parts, and the part where the length of the long side of the white part in each enlarged image reached 100μm or more was regarded as a pore. In each image divided into 100 parts, the area occupied by the white part was used as the porosity through image processing, and the average value of all porosities was used as the porosity. The case where the porosity is less than 8% is regarded as ○, the case where it is greater than 8% and less than 30% is regarded as △, and the case where it is greater than 30% is regarded as ×.

[0265] exist Figure 1 (a) shows a SAT image of the surface of the sintered body of the sample prepared in Example 3 after the die shear strength measurement. Figure 1 (b) shows a SAT image of the sintered body surface after the die shear strength measurement of the sample prepared in Comparative Example 2. In Example 3, no voids were observed, whereas in Comparative Example 2, a large number of voids were observed.

[0266] (4) SEM image results

[0267] For the samples prepared in the evaluation of the die shear strength, the center of the die was cut, and the cross section was polished using a grinding device. Then, the bonding cross section was observed using a scanning electron microscope at an adjusted magnification.

[0268] exist Figure 2 (a) shows a SEM image of a cross section of a sintered body of a sample prepared in Example 3 after the die shear strength measurement. Figure 2 (b) shows a SEM image of a cross section of a sintered body after the die shear strength measurement of the sample prepared in Comparative Example 2. In Example 3, generation of voids was not confirmed, whereas generation of voids was confirmed in Comparative Example 2.

[0269] (5) Comprehensive evaluation

[0270] The case where all the following evaluation criteria were satisfied was evaluated as ○, and the case where at least one of the criteria was not satisfied was evaluated as ×.

[0271] ·Printing rating: ○

[0272] ·Chip shear strength is over 30MPa

[0273] ·SAT rating: ○

[0274]

[0275] As shown in Table 1, the bonding conductor paste of the embodiment containing conductive particles, a dispersion medium including tripropylene glycol monomethyl ether as a hydroxyl-containing ether solvent, and further containing a given amount of a urea compound showed excellent printing suitability without being confirmed to have defects or bleeding in the printing evaluation. In the SAT evaluation, the generation of voids was also small, showing excellent bonding strength.

[0276] On the other hand, in Comparative Example 1 not containing a urea compound, the occurrence of voids was small in the SAT evaluation and excellent bonding strength was shown, but bleeding was observed in the printing evaluation.

[0277] Comparative Example 2, which contained a predetermined amount of urea compound but no hydroxyl-containing ether solvent as a dispersion medium, showed excellent bonding strength, but chipping and bleeding were observed in the printing evaluation, and a porosity of 30% or more was observed.

[0278] In Comparative Example 3 containing a urea compound in an amount exceeding a predetermined value, defects and bleeding were observed in the printing evaluation, and no sintering occurred in the die shear strength test. It is thought that the excessive urea compound coated the silver particles and hindered sintering.

[0279] In addition, in Comparative Example 4 containing a urea compound in a smaller amount than the prescribed amount, the occurrence of voids was small in the SAT evaluation and excellent bonding strength was shown, but bleeding was observed in the printing evaluation.

[0280] Modifications of the invention disclosed herein will be described below.

[0281] [Supplementary Note 1] A bonding conductor paste comprising conductive particles, a dispersion medium comprising a hydroxyl group-containing ether solvent, and a urea compound,

[0282] The content ratio of the urea compound is 1 to 20 parts by mass (preferably 2 to 15 parts by mass, more preferably 3 to 12 parts by mass) based on 100 parts by mass of the total dispersion medium containing the hydroxyl-containing ether solvent.

[0283] [Supplementary Note 2] A bonding conductor paste comprising conductive particles, a dispersion medium comprising a hydroxyl-containing ether solvent, and a urea compound,

[0284] The content ratio of the urea compound is 0.1 to 2 parts by mass (preferably 0.2 to 1.5 parts by mass, more preferably 0.3 to 1.2 parts by mass) based on 100 parts by mass of the conductive particles.

[0285] [Supplement 3] The bonding conductor paste according to Supplement 1 or 2, wherein the content ratio of the urea compound is 3 to 50 parts by mass (preferably 3.5 to 30 parts by mass, more preferably 4 to 20 parts by mass) relative to 100 parts by mass of the hydroxyl-containing ether solvent.

[0286] [Appendix 4] The bonding conductor paste according to any one of Appendices 1 to 3, wherein the content ratio of the urea compound is 0.09 to 1.8 parts by mass (preferably 0.15 to 1.4 parts by mass, more preferably 0.25 to 1.1 parts by mass) relative to 100 parts by mass of the total of the conductive particles and the dispersion medium.

[0287] [Appendix 5] The bonding conductor paste according to any one of Appendices 1 to 4, wherein the content of the urea compound is 0.09 to 1.8 mass % (preferably 0.15 to 1.4 mass %, more preferably 0.25 to 1.1 mass %) relative to 100 mass % of the total amount of the bonding conductor paste.

[0288] [Supplementary Note 6] The bonding conductor paste according to any one of Supplementary Notes 1 to 5, wherein the urea compound is at least one selected from modified urea, urea-modified urethane, polymer urea derivatives and urea-modified polyamides (for example, urea-modified medium-polarity polyamides, urea-modified low-polarity polyamides, etc.).

[0289] [Appendix 7] The bonding conductor paste according to any one of Appendices 1 to 6, wherein the conductive particles include silver particles.

[0290] [Supplementary Note 8] The bonding conductor paste according to any one of Supplementary Notes 1 to 7, wherein the conductive particles include conductive nanoparticles (A) having an average particle diameter of 1 nm or more and less than 100 nm (preferably 2 to 80 nm, more preferably 5 to 70 nm, and even more preferably 10 to 60 nm),

[0291] The conductive nanoparticles (A) are conductive nanoparticles having a structure in which the surface is coated with a protective agent containing amine.

[0292] [Supplementary Note 9] The bonding conductor paste according to Supplementary Note 8, wherein the protective agent in the conductive nanoparticles (A) is an amine.

[0293] An aliphatic hydrocarbon monoamine (1) comprising an aliphatic hydrocarbon group and one amino group, wherein the aliphatic hydrocarbon group has a total of 6 or more carbon atoms,

[0294] The invention further contains at least one of an aliphatic hydrocarbon monoamine (2) comprising an aliphatic hydrocarbon group and one amino group, wherein the total number of carbon atoms of the aliphatic hydrocarbon group is 5 or less, and an aliphatic hydrocarbon diamine (3) comprising an aliphatic hydrocarbon group and two amino groups, wherein the total number of carbon atoms of the aliphatic hydrocarbon group is 8 or less.

[0295] [Supplementary Note 10] The bonding conductor paste according to Supplementary Note 9, wherein the total amount of amines [monoamine (1) + monoamine (2) + diamine (3); 100 mol %] is in the following range:

[0296] Content of monoamine (1): 5 to 65 mol% (the lower limit is preferably 10 mol%, more preferably 15 mol%. The upper limit is preferably 50 mol%, more preferably 40 mol%, and further preferably 35 mol%)

[0297] Total content of monoamine (2) and diamine (3): 35 to 95 mol% (the lower limit is preferably 50 mol%, more preferably 60 mol%, and even more preferably 65 mol%. The upper limit is preferably 90 mol%, and more preferably 85 mol%).

[0298] [Supplementary Note 11] The bonding conductor paste according to Supplementary Note 9, wherein when a monoamine (2) and a diamine (3) are used simultaneously, the contents of the monoamine (2) and the diamine (3) are in the following ranges based on the total amount of amines [monoamine (1) + monoamine (2) + diamine (3); 100 mol %],

[0299] Monoamine (2): 5 to 70 mol% (the lower limit is preferably 10 mol%, more preferably 15 mol%. The upper limit is preferably 65 mol%, more preferably 60 mol%)

[0300] Diamine (3): 5 to 50 mol% (the lower limit is preferably 10 mol%. The upper limit is preferably 45 mol%, more preferably 40 mol%).

[0301] [Note 12] A bonding conductor paste according to any one of Notes 8 to 11, wherein the conductive particles, in addition to the conductive nanoparticles (A), further comprise spherical conductive particles (B) having an average particle size of 0.5 μm to 1 μm (preferably 0.6 to 0.9 μm) and flat conductive flakes (C) having an average particle size of 1 μm to 10 μm (preferably 2 to 5 μm).

[0302] [Supplement 13] A bonding conductor paste according to any one of Supplements 8 to 12, wherein the proportion of the conductive nanoparticles (A) in the total amount of the conductive particles (100 mass %) contained in the bonding conductor paste is 50 mass % or less (preferably 30 mass % or less, more preferably 20 mass % or less).

[0303] [Appendix 14] The bonding conductor paste according to any one of Appendices 8 to 13, wherein the proportion of the conductive nanoparticles (A) in the total amount of the conductive particles (100% by mass) contained in the bonding conductor paste is 5% by mass or more (preferably 10% by mass or more).

[0304] [Supplement 15] A bonding conductor paste according to any one of Supplements 12 to 14, wherein the content ratio of the spherical conductive particles (B) in the total amount of the above-mentioned conductive particles contained in the above-mentioned bonding conductor paste (100 mass%) is 30 mass% or more (preferably 40 mass% or more, more preferably more than 50 mass%) and 85 mass% or less (preferably 80 mass% or less, more preferably 70 mass% or less).

[0305] [Note 16] A bonding conductor paste according to any one of Notes 12 to 15, wherein the content of the flat conductive flakes (C) in the total amount of the conductive particles (100 mass%) contained in the bonding conductor paste is 10 mass% or more (preferably 15 mass% or more) and 65 mass% or less (preferably 50 mass% or less, more preferably 40 mass% or less).

[0306] [Note 17] A bonding conductor paste according to any one of Notes 12 to 16, wherein the total content of the conductive nanoparticles (A), spherical conductive particles (B) and flat conductive flakes (C) in the total amount (100% by mass) of the bonding conductor paste is 70% by mass or more (preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more) and is 99.5% by mass or less (preferably 99% by mass or less).

[0307] [Supplement 18] The bonding conductor paste according to any one of Supplements 1 to 17, wherein the boiling point (at 1 atmosphere) of the above-mentioned hydroxyl-containing ether solvent is 130°C or higher (for example, 130 to 300°C, preferably 140 to 280°C, more preferably 150 to 260°C, and further preferably 160 to 240°C).

[0308] [Appendix 19] The bonding conductor paste according to any one of Appendices 1 to 18, wherein the vapor pressure of the hydroxyl-containing ether solvent at 30°C is 0.01 to 10.0 mmHg (preferably 0.05 to 8.0 mmHg, more preferably 0.1 to 6.0 mmHg, and even more preferably 0.3 to 4.0 mmHg).

[0309] [Supplementary Note 20] The bonding conductor paste according to any one of Supplementary Notes 1 to 19, wherein the ether solvent containing a hydroxyl group is -1 The viscosity at 0.1 to 20 mPa·s (preferably 0.5 to 10 mPa·s, more preferably 1 to 9 mPa·s, and even more preferably 3 to 8 mPa·s).

[0310] [Appendix 21] The bonding conductor paste according to any one of Appendices 1 to 20, wherein the hydroxyl group-containing ether solvent contains a compound represented by the following formula (A).

[0311] R a -O-(R b -O) n -OH(A)

[0312] (In formula (A), R a represents an alkyl group, an aryl group or an aralkyl group, R b represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer greater than 1)

[0313] [Appendix 22] The bonding conductor paste according to Appendix 21, wherein the compound represented by the formula (A) has a boiling point of 130°C or higher (for example, 130 to 310°C, preferably 170°C or higher, more preferably 200°C or higher).

[0314] [Note 23] A bonding conductor paste according to any one of Notes 1 to 22, wherein the dispersion medium comprises an organic solvent (a), an organic solvent (b) and an organic solvent (c) satisfying the following formulas (1) to (6), and the organic solvent (a), the organic solvent (b) and the organic solvent (c) are different compounds from each other.

[0315] 150℃≤Ta≤250℃ (1)

[0316] 150℃≤Tb≤250℃ (2)

[0317] 250℃≤Tc≤350℃ (3)

[0318] δa≥10.0 (4)

[0319] δc≤9.0 (5)

[0320] δc≤δb≤δa (6)

[0321] [Wherein, Ta~Tc represent the boiling points of organic solvents (a)~(c), and δa~δc represent the Hansen solubility parameters of organic solvents (a)~(c).]

[0322] [Supplementary Note 24] The bonding conductor paste according to Supplementary Note 23, wherein the boiling point Ta of the organic solvent (a) satisfies 150°C<Ta<250°C (preferably 155°C≤Ta≤220°C, more preferably 160°C≤Ta≤200°C).

[0323] [Supplementary Note 25] The bonding conductor paste according to Supplementary Note 23 or 24, wherein the SP value δa of the organic solvent (a) is 10.3 or more (preferably 10.4 or more).

[0324] [Appendix 26] The bonding conductor paste according to any one of Appendices 23 to 25, wherein the SP value δa of the organic solvent (a) is 16.0 or less (or 15.0 or less).

[0325] [Appendix 27] The bonding conductor paste according to any one of Appendices 23 to 26, wherein the boiling point Tb of the organic solvent (b) satisfies 150°C<Tb<250°C (preferably 180°C≤Tb≤248°C, more preferably 200°C≤Tb≤245°C).

[0326] [Appendix 28] The bonding conductor paste according to any one of Appendices 23 to 27, wherein the SP value δb of the organic solvent (b) is 8.0 to 12.0 (preferably 8.5 to 11.0, more preferably 9.0 to 10.5).

[0327] [Appendix 29] The bonding conductor paste according to any one of Appendices 23 to 28, wherein a temperature difference between Tb and Ta [Tb-Ta] is 2° C. or more (preferably 5° C. or more, more preferably 10° C. or more).

[0328] [Appendix 30] The bonding conductor paste according to any one of Appendices 23 to 29, wherein the boiling point Tc of the organic solvent (c) satisfies 250°C < Tc < 350°C (preferably 250°C < Tc ≤ 320°C, more preferably 250°C < Tc ≤ 300°C).

[0329] [Appendix 31] The bonding conductor paste according to any one of Appendices 23 to 30, wherein the SP value δc of the organic solvent (c) is 8.7 or less (preferably 8.5 or less).

[0330] [Appendix 32] The bonding conductor paste according to any one of Appendices 23 to 31, wherein the SP value δc of the organic solvent (c) is 6.0 or more (or 7.0 or more).

[0331] [Appendix 33] The bonding conductor paste according to any one of Appendices 23 to 32, wherein the temperature difference between Tc and Tb [Tc-Tb] is 2°C or more (preferably 6°C or more, more preferably 10°C or more).

[0332] [Appendix 34] The bonding conductor paste according to any one of Appendices 23 to 33, wherein a temperature difference between Tc and Ta [Tc-Ta] is 30°C or more (preferably 50°C or more, more preferably 60°C or more).

[0333] [Appendix 35] The bonding conductor paste according to any one of Appendices 23 to 34, which satisfies δc<δb.

[0334] [Appendix 36] The bonding conductor paste according to any one of Appendices 23 to 35, which satisfies δb<δa.

[0335] [Supplementary Note 37] The bonding conductor paste according to any one of Supplementary Notes 23 to 36, wherein the difference between δb and δc [δb-δc] is 0.1 or more (preferably 0.2 or more, more preferably 0.5 or more).

[0336] [Supplementary Note 38] The bonding conductor paste according to any one of Supplementary Notes 23 to 37, wherein the difference between δb and δc [δb-δc] is 2.0 or less (preferably 1.5 or less, more preferably 1.3 or less).

[0337] [Supplementary Note 39] The bonding conductor paste according to any one of Supplementary Notes 23 to 38, wherein the difference between δa and δb [δa-δb] is 0.1 or more (preferably 0.2 or more, more preferably 0.5 or more).

[0338] [Supplementary Note 40] The bonding conductor paste according to any one of Supplementary Notes 23 to 39, wherein the difference between δa and δb [δa-δb] is 2.5 or less (preferably 2.0 or less, more preferably 1.8 or less).

[0339] [Appendix 41] The bonding conductor paste according to any one of Appendices 23 to 40, wherein a difference between δa and δc [δa-δc] is 1.5 or more (preferably 2.0 or more).

[0340] [Supplementary Note 42] The bonding conductor paste according to any one of Supplementary Notes 23 to 41, wherein the difference between δa and δc [δa-δc] is 5.0 or less (preferably 4.0 or less, more preferably 3.0 or less).

[0341] [Note 43] The bonding conductor paste according to any one of Notes 23 to 42, wherein the ratio of the organic solvent (a) to the total amount of the organic solvent (a), the organic solvent (b) and the organic solvent (c) (100% by mass) [organic solvent (a) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is 5 to 70% by mass (preferably 10 to 60% by mass, more preferably 15 to 50% by mass).

[0342] [Note 44] The bonding conductor paste according to any one of Notes 23 to 43, wherein the ratio of the organic solvent (b) to the total amount of the organic solvent (a), the organic solvent (b) and the organic solvent (c) (100% by mass) [organic solvent (b) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is 5 to 70% by mass (preferably 10 to 60% by mass, more preferably 15 to 50% by mass).

[0343] [Note 45] The bonding conductor paste according to any one of Notes 23 to 44, wherein the ratio of the organic solvent (c) to the total amount of the organic solvent (a), the organic solvent (b) and the organic solvent (c) (100% by mass) [organic solvent (c) / {organic solvent (a) + organic solvent (b) + organic solvent (c)}] is 5 to 70% by mass (preferably 10 to 60% by mass, more preferably 15 to 50% by mass).

[0344] [Appendix 46] The bonding conductor paste according to any one of Appendices 23 to 45, wherein the content of the organic solvent (c) is 20 to 400 parts by mass (preferably 30 to 300 parts by mass, more preferably 50 to 200 parts by mass) relative to 100 parts by mass of the organic solvent (a).

[0345] [Note 47] The bonding conductor paste according to any one of Notes 23 to 46, wherein the content of the organic solvent (b) is 10 to 200 parts by mass (preferably 20 to 150 parts by mass, more preferably 40 to 100 parts by mass) relative to 100 parts by mass of the total amount of the organic solvent (a) and the organic solvent (c).

[0346] [Note 48] The bonding conductor paste according to any one of Notes 1 to 47, wherein the content of the hydroxyl-containing ether solvent in the total amount (100 mass %) of the dispersion medium is 10 to 60 mass % (preferably 15 to 55 mass %, more preferably 25 to 45 mass %).

[0347] [Appendix 49] The bonding conductor paste according to any one of Appendices 1 to 47, wherein the dispersion medium consists only of the hydroxyl group-containing ether solvent.

[0348] [Note 50] The bonding conductor paste according to any one of Notes 1 to 49, wherein the content ratio of the above-mentioned hydroxyl-containing ether solvent is 1 to 15 parts by mass (preferably 1.5 to 12 parts by mass, more preferably 2 to 10 parts by mass) relative to 100 parts by mass of the above-mentioned conductive particles.

[0349] [Appendix 51] The bonding conductor paste according to any one of Appendices 1 to 50, wherein the content ratio of the above-mentioned dispersion medium is 4 to 20 parts by mass (preferably 5 to 15 parts by mass, more preferably 6 to 12 parts by mass) relative to 100 parts by mass of the above-mentioned conductive particles.

[0350] [Note 52] The bonding conductor paste according to any one of Notes 1 to 51, wherein the content ratio of the conductive particles is 70 to 99.5% by mass (preferably 80 to 98% by mass, more preferably 85 to 95% by mass) relative to 100% by mass of the total amount of the bonding conductor paste.

[0351] [Note 53] The bonding conductor paste according to any one of Notes 1 to 52, wherein the content ratio of the dispersion medium (especially the organic solvent) is 0.5 to 30 mass % (preferably 2 to 20 mass %, more preferably 5 to 15 mass %) relative to 100 mass % of the total amount of the bonding conductor paste.

[0352] [Note 54] A bonding conductor paste according to any one of Notes 1 to 53, wherein the content ratio of the hydroxyl-containing ether solvent is 0.5 to 15 mass % (preferably 1 to 13 mass %, more preferably 2 to 12 mass %) relative to 100 mass % of the total amount of the bonding conductor paste.

[0353] [Note 55] A bonding conductor paste according to any one of Notes 1 to 54, wherein the total content of the dispersion medium is 70 mass % or more (preferably 80 mass % or more, more preferably 90 mass % or more, and further preferably 95 mass % or more) relative to 100 mass % of the total amount of the bonding conductor paste.

[0354] [Note 56] A bonding conductor paste according to any one of Notes 1 to 55, wherein the bonding strength (according to JIS Z 3198) when a silver-plated copper substrate is bonded to a silver-plated Si chip via a sintered body of the bonding conductor paste is greater than 30 MPa (preferably greater than 40 MPa).

[0355] [Appendix 57] The bonding conductor paste according to any one of Appendices 1 to 56, wherein the porosity in the sintered body of the bonding conductor paste measured using an ultrasonic imaging device is 30% or less (preferably less than 8%).

[0356] [Supplementary Note 58] A sintered body obtained by sintering the bonding conductor paste according to any one of Supplementary Notes 1 to 57.

[0357] [Appendix 59] A joined structure formed by joining using a sintered body, wherein the sintered body is formed by sintering the joining conductor paste according to any one of Appendices 1 to 57.

[0358] [Supplementary Note 60] An electronic device comprising the sintered body described in Supplementary Note 58.

[0359] Industrial Applicability

[0360] The bonding conductor paste disclosed herein is suitable for forming conductor wiring and bonding structures for connecting electronic elements such as power semiconductor elements and LED elements.

Claims

1. A bonding conductor paste comprising: Conductive particles, A dispersion medium comprising a hydroxyl-containing ether solvent, and Urea compounds, The content ratio of the urea compound is 1 to 20 parts by mass based on 100 parts by mass of the entire dispersion medium containing the hydroxyl-containing ether solvent.

2. A bonding conductor paste comprising: Conductive particles, A dispersion medium comprising a hydroxyl-containing ether solvent, and Urea compounds, The content ratio of the urea compound is 0.1 to 2 parts by mass based on 100 parts by mass of the conductive particles.

3. The bonding conductor paste according to claim 1 or 2, wherein The hydroxyl-containing ether solvent comprises a compound represented by the following formula (A): R a -O-(R b -O) n -OH(A) In formula (A), R a represents an alkyl group, an aryl group or an aralkyl group, R b represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer of 1 or greater.

4. The bonding conductor paste according to claim 1 or 2, wherein The urea compound is at least one selected from modified urea, urea-modified urethane, polymer urea derivatives and urea-modified polyamide.

5. The bonding conductor paste according to claim 1 or 2, wherein The conductive particles include silver particles.

6. The bonding conductor paste according to claim 1 or 2, wherein The conductive particles include conductive nanoparticles (A) having an average particle diameter of 1 nm or more and less than 100 nm. The conductive nanoparticles (A) are conductive nanoparticles having a structure in which the surface is coated with a protective agent containing amine.

7. The bonding conductor paste according to claim 6, wherein The proportion of the conductive nanoparticles (A) in the total amount (100% by mass) of the conductive particles contained in the bonding conductor paste is 50% by mass or less.

8. The bonding conductor paste according to claim 6, wherein The protective agent in the conductive nanoparticles (A) comprises an aliphatic hydrocarbon monoamine (1), and further comprises at least one of an aliphatic hydrocarbon monoamine (2) and an aliphatic hydrocarbon diamine (3) as an amine. The aliphatic hydrocarbon monoamine (1) comprises an aliphatic hydrocarbon group and one amino group, and the total number of carbon atoms in the aliphatic hydrocarbon group is 6 or more, The aliphatic hydrocarbon monoamine (2) comprises an aliphatic hydrocarbon group and one amino group, and the total number of carbon atoms in the aliphatic hydrocarbon group is 5 or less, The aliphatic hydrocarbon diamine (3) comprises an aliphatic hydrocarbon group and two amino groups, and the total number of carbon atoms in the aliphatic hydrocarbon group is 8 or less.

9. The bonding conductor paste according to claim 6, wherein The conductive particles include, in addition to the conductive nanoparticles (A), spherical conductive particles (B) having an average particle size of 0.5 μm to 1 μm, and flat conductive flakes (C) having an average particle size of 1 μm to 10 μm.

10. The bonding conductor paste according to claim 9, wherein The total content of the conductive nanoparticles (A), the spherical conductive particles (B) and the flat conductive flakes (C) in 100% by mass of the total amount of the bonding conductor paste is 80 to 99.5% by mass.

11. The bonding conductor paste according to claim 1 or 2, wherein The dispersion medium comprises an organic solvent (a), an organic solvent (b) and an organic solvent (c), wherein the organic solvent (a), the organic solvent (b) and the organic solvent (c) are different compounds and satisfy the following formulas (1) to (6): 150℃≤Ta≤250℃ (1) 150℃≤Tb≤250℃ (2) 250℃≤Tc≤350℃ (3) δa≥10.0 (4) δc≤9.0 (5) δc≤δb≤δa (6) Wherein, Ta~Tc represent the boiling points of the organic solvents (a)~(c), respectively, and δa~δc represent the Hansen solubility parameters of the organic solvents (a)~(c), respectively.

12. A sintered body obtained by sintering the bonding conductor paste according to claim 1 or 2.

13. A joined structure formed by joining using a sintered body, wherein the sintered body is formed by sintering the joining conductor paste according to claim 1 or 2.

14. An electronic device comprising the sintered body according to claim 12.

Citation Information

Patent Citations

  • Jointing conductor paste

    JP2020194786A

  • Water ingress prevention structure

    JP2022146294A